Physics-informed neural network prediction of active earth pressures on counterweight retaining walls at embankment shoulders under translation mode - Hongyang Liu; Yu Yang; Wenbo Tu; M.Hesham El Naggar; Qiang Luo; Wenjun Luo; Jiayao Chen (Computers and Geotechnics, 2027)

Investigation on active site regulation and structure-activity relationship of Mn2O3@ZSM-5 composites for methane chemical looping combustion - Jiaying Liu; Xiaohong Gui; Wenjun Zhou; Wu Qin; Ling-Nan Wu; Zhen-Yu Tian (Fuel, 2026)

Novel PKP2 compound heterozygous mutations causing neonatal early-onset arrhythmogenic cardiomyopathy: insights into the synergistic pathogenicity of biallelic inactivation - Xiaobin Li; Wenjun Yu; Xiaolong Yuan; Zhengke Li; Runlin Leng; Xiang Gao; Guohua Yang (Functional & Integrative Genomics, 2026)

Distinct soil microbial community composition and structure: evidence from soil inside and outside the cattle farm - Qi Ding; Jiayi Li; Fengling Xue; Wenjun Cui; Shiguang Hu; Lingfeng Yu; Wanyue Huang; Lin Li; Ping Cheng (Brazilian Journal of Microbiology, 2026)

DBD/Fe(II)/peracetic acid pretreatment mitigates nanofiltration fouling in landfill leachate treatment via coupled oxidation-coagulation and plasma-assisted iron cycling - Chuanfei Zhang; Wenjun Yin; Zhangjie Yu; Xin Mao; Jinlong Wang; Bin Liu; Xiaobin Tang; Langming Bai; Guibai Li; Heng Liang (Chemical Engineering Journal, 2026)

A kidney-targeted MOF nanozyme combats calcium oxalate crystal-induced kidney injury - Xuhong He; Min Zhou; Zhengxin Liang; Shiyi Jin; Kunze Yu; Longxiyu Meng; Zhicong Tan; Jinming Xu; Jiaju Xu; Chongjun Xiang; Jingchao Wei; Wenjun Gao; et al. (Chemical Engineering Journal, 2026)

Nature-based interventions for university student stress and anxiety: Two randomized trials in urban campus settings - Xinxin Wang; Freddie Lymeus; Wenjun Yu; Terry Hartig (Urban Forestry & Urban Greening, 2026)

Interfacial engineered protein–polysaccharide–polyphenol complex high internal phase emulsions: From stabilization mechanisms to intelligent applications - Haiping Liang; Chuanlong Yu; Lingli Chen; Zhuangpeng Wang; Leiyan Wu; Suyun Lin; Xinyi Mao; Jia Liu; Hui Chen; Wenjun Wang (Trends in Food Science & Technology, 2026)

Thermal mechanisms reorganize, not merely attenuate, across the urban–rural gradient: A diurnal analysis of land surface temperature drivers in Changsha, China - Qianjun Wei; Dongxuan Zhou; Xinying Yang; Wenzhong Zhang; Siyu Fan; Wenjun Kuang; Shuchang Luo; De Yu; Jie Tan (Sustainable Cities and Society, 2026)

A duckweed–red light system for phosphate removal and recovery from low phosphate polluted water coupled with nutrient-rich biomass production - Cuicui Wei; Zhubin Hu; Yongqiang Liu; Leyi Zhao; Jinlan Xiao; Yu Gao; Kaize He; Yanlin Jin; Zhuolin Yi; Yang Fang; Wenjun Xiao; Xinbo Jian; et al. (Journal of Environmental Chemical Engineering, 2026)

Co-degradation detoxification of dichloromethane and n-hexane in a microbial electrolytic cell: metagenomic insights into degradation pathways and functional genes - Meng Wu; Hongfeng Lu; Wenjun Lin; Jun Hu; Zhiliang Yu; Jianming Yu (Journal of Environmental Chemical Engineering, 2026)

Arctic sea ice motion retrieval via vision foundation model and cross-sensor SAR - Tian Gao; Chaozhen Lan; Liang Lv; Fushan Yao; Chunxia Zhou; Wenjun Huang; Hanyang Yu; Yongxian Zhang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Consistent tangent operator for adaptive substepping explicit Runge–Kutta stress integration: A study on the Modified Cam Clay model - Jinlong Xie; Yongjie He; Qianhui Liu; Wenjun Ji; Yuzhen Yu (Computers and Geotechnics, 2026)

Carbon dot-based gel-state emissive layer for light-emitting-diode with pure white emission - Dongren Zheng; Tianyang Zhang; Haizhou Yu; Xiangyong Meng; Wenjun Yang; Hui Huang; Cheng Zhu; Yang Liu; Zhenhui Kang (Chemical Engineering Journal, 2026)

A versatile near-infrared fluorescent probe for Zn2+ detection in food and biological matrices - Tianjiao Hou; Chunlin Fan; Hong Deng; Yifei Sun; Wenjun Miao; Chunyuan Hou; Yu Zhang; Jun Luo; Xuan Shen (Analytica Chimica Acta, 2026)

Repair strategy and residual strength analysis of damaged marine carbon fiber composite sandwich panel: repair test and numerical verification - Shichen Zhang; Shuangxi Xu; Wenjun Tang; Yu Qiu; Yigang Wu; Wei Shen (Ocean Engineering, 2026)

Reconstructing lattice Cu2+ to surface Cu0 in CuCo spinel drives reverse charge transfer for selective peracetic acid activation toward water decontamination - Hao Chen; Quan Wang; Wenjun Gao; Sha Yu; Hongying Zhao; Yuanzhen Zhou (Journal of Hazardous Materials, 2026)

The independent and joint effects of short-term exposure to ambient air pollutants on eczema in two cities of China - Tianjing Ouyang; Zhuoxuan Liang; Shujie Huang; Yingyin Liu; Ziqiang Lin; Qijiong Zhu; Weiquan Zeng; Yu Wang; Changchang Li; Jianxiong Hu; Guanhao He; Tao Liu; et al. (Journal of Hazardous Materials, 2026)

A transfer learning-based contourlet residual-driven terrain-aware method for Arctic seafloor DEM super-resolution - Wenjun Huang; Qun Sun; Qing Xu; Jingzhen Ma; Zheng Lv; Tian Gao; Anzhu Yu (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Comparative effects of liquid nitrogen rapid freezing, micro-freezing liquid-assisted freezing, and conventional freezing on the physicochemical properties, moisture distribution, microstructure, and protein characteristics of beef steaks - Ling Jiang; Donghong Liu; Wenjun Wang; Ruiling Lv; Songfeng Yu; Yunli Deng; Jianwei Zhou (Food Control, 2026)

Evaluation of Rice Yield Attributes, Loach Muscle Quality, and Soil Biochemical Composition Under Rice–Loach Coculture System - Chuanqi Yu; Wenlu Zhu; Wenjun Wang; Wenqiang Xu; Yu Liu; Xingtian Cai; Yanfa Xu; Defu Yang; Zhuqing Yang; Zirui Wang; Qiubai Zhou; Haohua He (Fishes, 2026)
This study aimed to evaluate rice yield attributes, loach Paramisgurnus dabryanus muscle quality, and soil biochemical composition under rice monoculture (RM), rice–loach coculture (RLC), and loach monoculture (LM). This trial was conducted for 90 days, and then rice, fish muscle and soil were obtained for analyses. The results showed that there were no significant differences in rice yield attributes between the rice–loach coculture (RLC) and rice monoculture (RM) groups. However, rice–loach coculture (RLC) improved muscle quality-related parameters, including increased hardness and springiness of loach muscle. Meanwhile, muscle metabolomic analysis showed that all the differentially expressed metabolites (DEMs) in the significantly enriched pathways of lysine degradation and lysine biosynthesis were up-regulated in the rice–loach coculture (RLC) group compared with the loach monoculture (LM) group. Furthermore, the rice–loach coculture (RLC) improved soil physicochemical properties, including an increase in microbial biomass nitrogen (MBN) content and activities of soil N-acquiring enzymes (NAG and LAP). Moreover, soil microbiome analysis showed that the abundance of Candidatus Koribacter versatilis, Acidobacteria bacterium WX27 and Pseudolabrys taiwanensis was significantly increased in the rice monoculture (RM) and rice–loach coculture (RLC) groups compared with the loach monoculture (LM) group. Pairwise Spearman’s correlation analysis of the top 30 soil microbial species and soil physicochemical properties indicated that Terrimonas sp. H1YJ31 showed a highly significant positive correlation with the soil N-acquiring enzymes (N-acetylglucosaminidase, NAG; leucine aminopeptidase, LAP) and a soil C-acquiring enzyme (exo-β-1,4-glucanase C1), whereas Gaiella occulta, Methyloceanibacter marginalis and Anaerohalosphaera lusitana had a highly significant negative correlation with S-NAG, S-LAP and S-C1. In short, the improved fish muscle quality and soil biochemical composition were ascribed to the increased hardness and springiness of loach muscle and the abundance of soil Terrimonas sp. H1YJ31.

Biallelic hexose-6-phosphate dehydrogenase variants cause mitochondrial dysfunction underlying Parkinson’s disease - Miao Zhao; Yuwen Zhao; Juan Huang; Yu Guo; Wenjun Yu; Haiyan Hou; Yilin Huang; Xinying Du; Yu Zhang; Mujun Xie; Zuowen Ren; Haoyu Guan; et al. (Science Bulletin, 2026)

Omics-assisted genetic dissection and coordinated improvement of apple flesh color, flavor, and fruit size - Nan Wang; Wenjun Liu; Xuelian Han; Zhiqiang Li; Xin Jing; Zongying Zhang; Hongcheng Fang; Shuhui Zhang; Haifeng Xu; Qi Zou; Lei Yu; Tongyao Xu; et al. (Molecular Plant, 2026)

Effects of impurities on the rheological behavior of rare earth concentrate slurry and the regulatory role of retarders - Xiaodong Wang; Xiaowei Zhang; Feng Guo; Yanhong Hu; Jinxiu Wu; Wenjun Fan; Likai Zang; Qifu Yuli; Zhao Yu; Ruifeng Ma (Minerals Engineering, 2026)

Promoting the excitation of ferrate(VI) with copper oxide nanoparticles for the degradation of 2,4-dichlorophenol - Guihai Zhang; Yidan Luo; Wenjun Zeng; Yingshuai Zhang; Jiancheng Cheng; Xinlong Hua; Mengqin Yu; Yalan Zhang; Wei Liu; Xianchuan Xie; Zugen Liu (Journal of Water Process Engineering, 2026)

CFN: A Coarse-to-Fine 3D FaultSeg Network with directional modeling - Wenting Zhang; Haibo Ji; Yu Kang; Ji Chang; Wenjun Lv (Journal of Applied Geophysics, 2026)

Multiplexed electrochemical biosensors: system-level design frameworks, signal decoding strategies and translational perspectives for food safety - Shuyu Zhou; Yingyu Wu; Yi Li; Wenjun Yu; Danting Yang (Food Research International, 2026)

Resveratrol and tomato pectin synergistically ameliorated metabolic disorder in high-fat-diet mice through the microbiota-gut-liver axis - Xin Zong; Wenjun Liu; Ruiqi Wang; Wenting Zhao; Dan Wang; Songsong Jiang; Peiyou Qin; Yu Peng; Feng Lu; Xiaoyan Zhao; Pan Wang (Food Research International, 2026)

A cost-effective water cooled PEMFC bipolar plate with metal mesh flow field employing 2D fabrication process - Wenjun Li; Ruonan Ding; Weichang Gu; Wenrong Shi; Yingchao Shang; Liuyuan Han; Yang Liu; Yang Li; Fangyong Yu; Zhen Guo (Chemical Engineering Journal, 2026)

Characteristics and Dry Deposition Fluxes of Particulate Parent, Alkyl, and Nitro-Polycyclic Aromatic Hydrocarbons in the Bohai Sea Strait, China - Xinyuan Kang; Mian Li; Wenjun Yao; Hao Sun; Zilan Wu; Limin Yu; Xindong Ma (Atmospheric Environment, 2026)

Corrigendum to <‘Circulating exosome-mediated AMPKα–SIRT1 pathway regulates lipid metabolism disorders in calf hepatocytes’> <[Research in Veterinary Science 169 (2024) /105177]> - Daoliang Zhang; Hongyan Ding; Chang Liu; Yingying Huang; Wenjun Tai; Shibin Feng; Xichun Wang; Chang Zhao; Yu Li (Research in Veterinary Science, 2026)

Characterization of polystyrene microplastics-derived organic matter and the effects on tetracycline photodegradation - Wenjun Yuan; Yu Sun; Qiuya Zhang; Jinmei Xu; Xia Xu; Jinlan Zhang (Journal of Water Process Engineering, 2026)

Identifying priority urban ecological restoration areas using an integrated machine-learning and multi-dimensional diagnostic framework - Yuxia Hu; Zhaowu Yu; Jinyu Hu; Wenjun Yang; Yujia Zhang; Yuxuan Wang; Yuhui Miao (Journal of Environmental Management, 2026)

A novel framework for quantifying ecosystem quality by coupling urban morphology - Yuxia Hu; Zhaowu Yu; Wenjun Yang; Jinyu Hu; Mingchuan Shao; Weiyuan Ma; Junhong Zhong; Ping Wu (Journal of Environmental Management, 2026)

Structural similarity analysis and AI-predicted binding mode of bitter flavonoids in pomelo (Citrus maxima) using HRMS-based metabolomics and molecular fingerprinting - Han Wang; Lu Peng; Runan Zhao; Songfeng Yu; Wenjun Wang; Donghong Liu (Food Research International, 2026)

Optimizing solvation structure of electrolyte to improve ion transport and reduce interphase resistance for fast-charging Li-ion batteries - Yiyi Zheng; Jiapei Li; Tian Zhang; Shuyu Dong; Qiaohui Duan; Zhiqiang Guan; Dewu Lin; Wenjun Zhang; Denis Y.W. Yu (Chemical Engineering Journal, 2026)

Construction of a scaffold-mediated dual-enzyme display system in Komagataella phaffii with immobilized cells for continuous biocatalysis - Chaowei Zhou; Fanyu Chen; Jing Leng; Caice Liang; Yu Sha; Wenjun Sun; Huanqing Niu; Yong Chen; Hanjie Ying (Bioresource Technology, 2026)

A near-infrared dual-channel fluorescent probe for ultrasensitive detection of Zn2+ and Cd2+ in food safety and bioimaging applications - Tianjiao Hou; Hong Deng; Xuan Zhou; Duxiao Zhang; Wenjun Miao; Chunyuan Hou; Yu Zhang; Jun Luo; Xuan Shen (Food Chemistry, 2026)

Change of global precipitation during strong El Niño under high-emission scenarios - Wenjun Sang; Yu Huang; Zhigang Cheng; Yaohui Li; Lian Duan; Wenwen Xu; Ruping Zhang (Frontiers of Earth Science, 2026)

Quantifying evapotranspiration and shading cooling of urban vegetation across climates under extreme heat using an integrated SCOPE-SEB model and surface temperature analysis - Zhaowu Yu; Mingchuan Shao; Wenjun Yang; Yujia Zhang; Yuxia Hu; Wenjuan Ma; Junhong Zhong; Yanghan Lin; Mincong Wang; Huiwen Zhang; Jiquan Chen; Chenghao Wang; et al. (Remote Sensing of Environment, 2026)

ESMDA-BaPC: an efficient bayesian surrogate approach for contaminant source identification - Guodong Zhang; Teng Xu; Wenjun Zhang; Jie Yang; Yu Ye; Chunhui Lu (Journal of Hydrology, 2026)

Dual modulation of ion–water and ion–electrode interactions enabled by water-in-ionic-liquid electrolytes for robust metal-free batteries - Yu Meng; Yibing Yang; Mingzi Sun; Shaozhuan Huang; Bolong Huang; Wenjun Zhang; Shuilin Wu (Chemical Engineering Journal, 2026)

Ionic liquid tailored poly(ethylene glycol) acylurea networks enabling thermo switchable crystallinity for recyclable iontronic sensing and thermally programmed actuation - Yu Zhang; Yuting Jiang; Yunsheng Xu; Pengwu Xu; Wenjun Peng; Weijun Yang; Shuangfei Xiang; Xianming Zhang (Chemical Engineering Journal, 2026)

Interfacial biomimetic engineering synergizing with mycelium: Constructing high-strength, water-resistant, and flame-retardant formaldehyde-free composites - Junqiang Shan; Yajuan Cao; Yanjun Chen; Yingye Shen; Tianpeng Chen; Yu Sha; Wenjun Sun; Yong Chen; Hanjie Ying (Chemical Engineering Journal, 2026)

Engineering Escherichia coli cell Factories for continuous 5′-cytidine monophosphate production via biofilm-anchored dual-enzyme cascade catalysis - Wenjun Sun; Shiya Zhu; Qiwei Dong; Shuyan Tang; Qingguo Liu; Yu Sha; Tianpeng Chen; Rui Wang; Yong Chen; Hanjie Ying (Bioresource Technology, 2026)

Diosmetin, an active ingredient of Schizonepeta tenuifolia, alleviates acne by regulating inflammation and oxidative stress - Yu Pan; Rui Sun; Elizabeth Rosalind Thomas; Shi Pan; Linli Yang; Wenjun Wang; Lin Chen; Xiang Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Plant protein complex prepared from legume protein and cereal protein: sources, techniques and challenges - Wei Zhou; Wenjun Wang; Hong Wang; Songfeng Yu; Yue Zhao; Jiao Ge; William Nicholas Ainis; Wei Zhang; Tengfei Yu; Shiguo Chen; Donghong Liu; Guanchen Liu (Critical Reviews in Food Science and Nutrition, 2026)

C-type porous starch microgels for robust lutein Mickering emulsions - Can Zhao; Yu Cheng; Wenjun Li; Li Yuan; Xingbin Yang; Zhong Zhang (Journal of Food Engineering, 2026)

Dual-heteroatoms codoping protocol selectively controls nonradical pathway in peroxymonosulfate-based Fenton-like reaction - Zhendong Zhao; Yu Wan; Qianqian Wu; Tong Hu; Huiwang Dai; Wenjun Zhou (Journal of Environmental Chemical Engineering, 2026)

Flame-synthesized LaMnO3 as a high-efficiency oxygen carrier for methane chemical looping combustion: Structure-activity relationship and reaction pathways - Jiaying Liu; Xiaohong Gui; Wenjun Zhou; Wu Qin; Ling-Nan Wu; Zhen-Yu Tian (Chemical Engineering Journal, 2026)

Multiscale mechanistic study into cellulose pyrolysis and Co-pyrolysis with polyethylene via ReaxFF molecular dynamics and experimental validation - Yu Zhang; Muhammad Sajjad Ahmad; Wenjun Zhou; Yingna Li; Rongpu Cao; Boxiong Shen (Chemical Engineering Journal, 2026)

Development and Application of a Method to Enhance Lipase Performance and Wastewater Treatment Capacity Using DES - Jiaxin Song; Chuanlong Yu; Fangling Wu; Li Yuan; Danna Fan; Yiheng Zhang; Yuping You; Guoqiang Wu; Zedong Zhang; Wenjun Wang (Sugar Tech, 2026)

Constructing the purification-permeability balance via polymerization route: a novel confined layered double hydroxide catalytic membrane incorporating single-atom iron - Yufei Wang; Xiaomeng Yu; Wenjun Wu; Zaicheng Sun; Hui Wang; Jin Guo (Water Research, 2026)

Benzyl isothiocyanate inhibits the conjugative transfer of mcr-1-positive plasmid via suppressing intercellular contact and limiting energy supply - Ping Cheng; Shuying Liang; Shixin Gui; Xinyu Wang; Lingfeng Yu; Wenjun Cui; Chunxu Lu; Lin Li (Journal of Environmental Management, 2026)

Mediating role of the maternal placental growth factor levels on association between ozone exposure and adverse pregnancy outcomes - Yajuan Wang; Yuanyuan Yu; Yang Li; Xiaoli Gao; Wenjun Fan; Xuening Bai; Xiaozhou Li; Jiayan Zhou; Ying Zhang; Qisijing Liu; Chen Li; Rongrong Wu; et al. (Environmental Research, 2026)

Engineering Escherichia coli for continuous L-valine production via two-stage biofilm and metabolic regulation - Wenjun Sun; Yu Sha; Shuqi Shi; Wenlu Qi; Qingguo Liu; Tianpeng Chen; Yong Chen; Hanjie Ying (Chemical Engineering Journal, 2026)

Engineering living bio-hybrid materials for sustainable l-threonine production - Shuqi Shi; Jinming Zhang; Shiya Zhu; Yu Sha; Qingguo Liu; Tianpeng Chen; Wenjun Sun; Wei Zhuang; Yong Chen; Hanjie Ying (Bioresource Technology, 2026)

Large Potential for CH 4 Mitigation and Yield Improvement in China's Paddies Through Locally Optimized N Management - Haoyu Qian; Zhengqi Yuan; Xiangcheng Zhu; Yuanfa Huang; Min Li; Jiarui Li; Yuxin Ren; Jinfei Feng; Shan Huang; Wenjun Dong; Feng Jin; Jiping Gao; et al. (Global Change Biology, 2026)
Nitrogen (N) management is critical for ensuring food security and mitigating greenhouse gas (GHG) emissions. In rice paddies, the effectiveness of N management in maximizing yields and minimizing N losses is highly dependent on local environmental conditions and thus varies widely across regions. However, the influence of optimized, site‐specific N management on methane (CH 4 ) emissions remains poorly quantified and is not reflected in current IPCC Tier 1 methodologies. Here, we synthesize data from multiregional field experiments and conduct a meta‐analysis to show that locally optimized N management practices—such as delayed fertilizer application, reduced N input, and deep placement—reduce CH 4 emissions from rice paddies by 16%–21%. The experiments further show that these practices suppress CH 4 emissions by lowering soil N availability and organic matter decomposition, thereby limiting substrates for methanogenesis. Combining survey data from 155 counties with machine learning models, we estimate that implementing optimized N strategies across China's rice‐growing regions could reduce CH 4 emissions by 16% while simultaneously increasing rice yields by 7%. These findings underscore the dual benefits of locally optimized N management for agricultural productivity and climate change mitigation, and provide a foundation for improving CH 4 emission estimates under diverse management regimes.

DNMT1-mediated LAMA2 inhibition induces M2 macrophage polarization during prostate cancer progression - Ruiqian Li; Chen Hu; Fengming Ran; Yu Bai; Hongyi Wu; Wenjun Peng; Yixuan He; Qilin Wang; Jun Li (Tissue and Cell, 2026)

Intensive flooding enhances methane but reduces carbon dioxide and nitrous oxide emissions in reservoir drawdown areas - Wenjun Shi; Manuel Delgado-Baquerizo; Hao Liao; Yu Gong; Guiyao Zhou; Siyue Li; Hao Jiang; Yuyi Yang; Chen Ye; Quanfa Zhang (Environmental Research, 2026)

Propagation characteristics of projected meteorological to hydrological droughts in the Poyang Lake Basin - Yining Xie; Yanzhong Li; Dan Zhang; Wenjun Yu; Haiwen Yan; Huan Wu (Theoretical and Applied Climatology, 2026)

Gut microbiota as a causal mediator linking inflammatory cytokines and ageing phenotypes - Qiyu Liu; Weidong Li; Wuliang Diao; Wenjun Shi; Li Yu; Yuchen Cai; Xueyao Cai (Biogerontology, 2026)

Atmospheric emission inventory of trace elements from non-ferrous metal smelting industries in China - Yiping Lu; Xiaoxuan Bai; Zhiqiang Fu; Junqi Yang; Yu Zhou; Wenjun Liu; Yan Hao; Hongyan Zhao; Hezhong Tian (Resources, Conservation and Recycling, 2026)

A function-triggered framework for the feasibility analysis of autonomous ships in Arctic pendulum transport mode - Wenjun Zhang; Gang Wu; Xiang-Yu Zhou; Xue Yang; Xiangkun Meng (Regional Studies in Marine Science, 2026)

Ethylene production from chlorinated organic hazardous wastes by thermal plasma pyrolysis - Yanping Yu; Hao Li; Wenlong Dong; Jiachen Zhu; Jiaqi Xu; Chen Wang; Baogen Su; Wenjun Zhang; Zhongbiao Wu; Qilong Ren; Qiwei Yang (Journal of Hazardous Materials, 2026)

Polylactic acid microplastics inhibit Cd accumulation and growth of Solanum nigrum L.: Insights from microbial communities and metabolomic profiles - Lei Xu; Chufei Yu; Qingjian Zhang; Xiuxiu Yan; Shuhe Wei; Wenjun Xie; Lidia Skuza; Yunqing Jing; Yuhan Sun; Shuyi Wang; Cailing Shi; Huiping Dai (Environmental Research, 2026)

Tannic acid-triggered functional coatings for the regulation of surface charge, cell adhesion and semi-continuous fermentation - Yu Sha; Yong Gao; Jinming Zhang; Tianpeng Chen; Qingguo Liu; Chenjie Zhu; Pengpeng Yang; Hanjie Ying; Yong Chen; Wenjun Sun; Wei Zhuang (Journal of Environmental Chemical Engineering, 2025)

Impact of KCl and L-Arg substitution on low salt beef patties: oxidative, textural, flavor, and microbial insights - Chuanlong Yu; Lingli Chen; Hui Chen; Suyun Lin; Wenbing Hu; Kehui Ouyang; Wenjun Wang (Food Chemistry, 2025)

Efficacy and antibacterial mechanism of intense pulsed light against Escherichia coli: Photochemical and physical effect - Zihan Ye; Tingting Chen; Ruyu Zhang; Ruiling Lv; Songfeng Yu; Jianwei Zhou; Wenjun Wang; Donghong Liu (Food Bioscience, 2025)

Vertically aligned cellulose-based aerogel via low-cost ambient drying for efficient solar-driven evaporation - Haoran Shi; Changhui Wang; Wenjun Huang; Fei Guo; Rilong Yang; Jianguo Li; Jiandong Zhuang; Hui Zhang; Yan Yu; Xuexia Zhang (Chemical Engineering Journal, 2025)

Engineered nanotechnology for epigenetic therapy in cancer treatment - Yan Li; Yang Li; Yuan Tan; Yanan Cai; Xinfeng Liu; Chao Wei; Wenjun Yu; Yuanlei Fu; Haiqiang Cao (Chemical Engineering Journal, 2025)

Defect-mediated permeation of deep eutectic solvents in cellulose crystals: A combined experimental and molecular dynamics study - Yuanhong Yu; Xianyu Song; Yanglong Wang; RuiPeng Lai; Yuxiang Nie; Wenjun Xiang; Chuxiang Zhou; Shuangliang Zhao; Honglai Liu (Carbohydrate Polymers, 2025)

Hypoxia-induced S100A10 promotes glioblastoma malignancy and chemoresistance by activating PI3K-AKT signaling pathway - Qingqing Yang; Yunlan Xi; Xuewei Huang; Wenzhe An; Cuiyun Sun; Qian Wang; Dan Hua; Wenjun Luo; Cuijuan Shi; Hongli Pan; Zhendong Jiang; Bingkun Wang; et al. (Functional & Integrative Genomics, 2025)

Altitude regulates the response of nitrogen removal function to short-term flooding events in a riparian ecotone - Yu Gong; Xiaoling Li; Xiaodie Duan; Wenjun Shi; Siyue Li; Chen Ye; Quanfa Zhang (Water Research, 2025)

Enhanced prediction of ultimate bearing capacity of FRP-concrete-steel double-skin tubular columns using interpretable models and intelligent optimization algorithm - Shiying Liu; Haoran Liu; Yu Zhong; Jinqiu Liu; Wenjun Ou; Wei Liang; Zhanyuan Zhu; Shucheng Yuan; Bing Ma (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

A stabilized equal-order linear polygonal and polyhedral scaled boundary finite element formulation for Biot’s consolidation problems in saturated soils - Wenjun Ji; Qingshuo Hao; Chongmin Song; Qianhui Liu; Yuzhen Yu (Computers and Geotechnics, 2025)

Bidirectional interphase modulation of ionic liquid-based additive for highly compatible thin-film lithium-metal batteries - Wenjun Lin; Haoyang Yuan; Tao Huang; Aishui Yu (Chemical Engineering Journal, 2025)

A dual-mode response fiber paper-based sensor based on curcumin and sodium alginate for soil moisture monitoring - Yu Zhou; Ruqiang Zhang; Youping Tang; Yifeng Huang; Weidong Zhang; Yulong Hu; Xichao Liang; Wenjun Li; Ling Yang; Zhu Long (Chemical Engineering Journal, 2025)

Effects of stringent industrial control during the Beijing Winter Olympics on bacterial variations in the atmosphere and built environments - Zhuo Chen; Fanxuan Xia; Yan Wang; Wuwei Zou; Jiyi Mi; Zhiwei Li; Tao Yu; Wenjun Leng; Jinhan Mo (Building and Environment, 2025)

Synergistic impacts of Atlantic multidecadal oscillation and Indian Ocean Dipole on the decadal intensification of the warm season heatwaves in China - Qiang Gu; Yixing Yin; Shibao Dai; Shuang Liu; Shanlei Sun; Xiaojun Long; Peng Deng; Yanzhong Li; Wenjun Yu (Atmospheric Research, 2025)

The frequency, intensity, and alternation timing of dry-wet abrupt alternation events and the possible correlation with the summer rain belt/season in China - Shuang Liu; Ying Chen; Yixing Yin; Qiang Gu; Xiaojun Long; Yanzhong Li; Wenjun Yu; Pengnian Huang (Atmospheric Research, 2025)

Nitrogen addition and precipitation reduction regulate soil organic carbon storage with contrasting mechanisms in subtropical forests - Rudong Zhao; Chang Liao; Yu Wu; Qiuxiang Tian; Qinghu Jiang; Xiaoxiang Zhao; Wenjun Li; Feng Liu (Plant and Soil, 2025)

A ratiometric dual-channel fluorescent probe for selective Zn2+/Cd2+ sensing: Applications in food quality control, real-time monitoring in living cells, and mice - Hong Deng; Tianjiao Hou; Xuan Zhou; Duxiao Zhang; Wenjun Miao; Chunyuan Hou; Yu Zhang; Jun Luo; Xuan Shen (Analytica Chimica Acta, 2025)

Effects of bamboo nano-biochar on sandy loam nitrogen and phosphorus leaching loss and water infiltration capacity - Junfeng Tang; Aoyang Jiang; Wenjun Chen; Jinghao Rao; Meiqin Zhou; Zhuxiang Ma; Yu Deng; Sitong Li (Science of The Total Environment, 2025)

Study on the mechanism of different doses of lycium barbarum polysaccharides affecting sperm motility in Drosophila melanogaster - Jingjing Yu; Wenjun Fu; Xinyi Wang; Xiang Zhang; Kun Xiong; Yuan Wang (Reproductive Toxicology, 2025)

Critical hydro-geomorphological characteristics related to lateral erosion–deposition difference within the multilevel bifurcation system of the Yangtze Estuary, China - Boyuan Zhu; Shiyu Zhang; Lingling Zhu; Lingfeng Liu; Wenjun Yu; Jinwu Tang; Yongzhou Cheng; Yitian Li; Alistair G.L. Borthwick (Journal of Hydrology, 2025)

Maternal placental growth factor mediates the association between PM2.5 and its constituents with adverse pregnancy outcomes - Yuanyuan Yu; Wenjun Fan; Jiayan Ni; Xiaoli Gao; Weixia Li; Jianqiong Zheng; Hongping Zhang; Juan Chen; Qisijing Liu; Zi Lin; Bin Chen; Yajuan Wang; et al. (Journal of Hazardous Materials, 2025)

Insight into pyrolysis mechanism of p-aminophenol crystal based on thermogravimetric analysis and ReaxFF molecular dynamics - Wenjun Zhou; Zhi-Min Wang; Zhen-Yu Tian (Fuel, 2025)

ACE-inhibitory peptides from Morchella esculenta: screening, kinetics, and molecular dynamics simulation - Wenjun Zeng; Xudong Yu; Mingfeng Chen; Huiling Zhang; Jucai Xu; Xiaofang Zeng; Ying Liang (Food Chemistry, 2025)

Lipidomics revealed the geographical origin and breed variability of sheep milk - Hai-Long Wang; Xiaoyin Chen; Xiaoyu Peng; Yu Gao; Jiaqi Wang; Wei Li; Chinping Tan; Yuan fa Liu; Wenjun Zou; Yong-Jiang Xu (Food Bioscience, 2025)

Bifidobacterium adolescentis CCFM1386 relieved prediabetes symptoms by modulating gut microbiota and metabolic profiles in mice - Xihua Yu; Yurong Zhao; Yi Wang; Liuruolan Li; Wenwei Lu; Wenjun Wu; Hongchao Wang (Food Bioscience, 2025)

Excellent energy storage density of Bi-doped CaTiO3 linear dielectrics - Kun Chen; Wenjun Cao; Yanwei Wu; Chao Cheng; Yingtang Zhang; Jun Zheng; Shouguo Huang; Yi Yu; Chunchang Wang (Chemical Engineering Journal, 2025)

Research progress in the technology of active substance extraction from red algae - Jinqi Qu; Runze Liu; Wensong Yu; Wenjun Li; Chenyang Lu; Song Qin (Algal Research, 2025)

Spatial–Temporal Dynamics of Drought Characteristics and Its Influencing Factors on Tibetan Plateau - Zhizhu Zhou; Wenjun Yu; Lin Zhao; Yanzhong Li; Shuo Cheng; Jiazhe Duan; Yincong Xing; Wei Shao (International Journal of Climatology, 2025)
Assessing drought on the Tibetan Plateau (TP) is essential for understanding the spatial characteristics of the region's hydrological regimes, as well as the trends of the evolving climate‐ecological system. Based on the precipitation and the potential evapotranspiration data from the ERA5‐Land dataset, this study evaluated the drought characteristics on the TP from 1950 to 2022 using the Standardised Precipitation Evapotranspiration Index (SPEI) and the Run theory. The analysis of SPEI at multiple time scales—SPEI‐1 (monthly), SPEI‐3 (seasonal), and SPEI‐12 (annual)—consistently revealed a pronounced drying trend across the TP over the past 70 years. Notably, the wet‐to‐dry transition points were detected in 2000 and 2001 based on the SPEI‐1 and SPEI‐3 series, respectively, while the SPEI‐12 series indicated a later shift occurring in 2004. In addition, the SPEI values indicated a spatial trend of increasingly severe drought conditions from south to north. Particularly, pronounced drought stress was observed in the Brahmaputra, Ganges, and Indus basins, as well as in the southern regions of the Inner Plateau. Furthermore, the relationships between drought variability and key climatic drivers—including sunspots, El Niño‐Southern Oscillation (ENSO), temperature (TEMP), and annual mean areal precipitation (AP)—were identified through cross‐wavelet transform (XWT) and wavelet coherence analysis (WTC). In general, the analysis showed that the SPEI values on the TP were negatively correlated to ENSO and TEMP but positively correlated to sunspots and AP. This study offers a comprehensive spatiotemporal assessment of drought dynamics across the TP, providing critical insights for regional water resource management and climate change adaptation planning.

Lipid droplet clearance inhibits esophageal cancer growth via metabolic reprogramming - Yan Pu; Yi Wan; Yuhua Fu; Kai Li; Yijiao Chen; Yunzhi Wang; Bin Li; Lingling Li; Zhaoyu Qin; Jingyan Xu; Dongxian Jiang; Yan Li; et al. (Science Bulletin, 2025)

Washing remediation of arsenic-contaminated soil from mining areas using an efficient and eco-friendly agent: Screening, optimization, properties, and risk assessment - Tingting DENG; Chufei YU; Qingjian ZHANG; Lei XU; Wenjun XIE; Huiping DAI; Lidia SKUZA; Jie ZHAN; Yuhan SUN; Shuyi WANG; Shuhe WEI (Pedosphere, 2025)

Dual-conjugation of aminated sugar beet pectin-oxidized tannic acid nanonetworks with cinnamaldehyde at the oil-water interface to stabilize a 3D printable high internal phase emulsion - Hualei Chen; Shujuan Yu; Fei Pan; Xiangxin Li; Xiaoming Fang; Wenjun Peng; Wenli Tian (Food Chemistry, 2025)

High-rate and long-cycle sodium dual-ion batteries via extended π-conjugated polymer for −45-60 °C operation - Wenjun Li; Yang Gu; Yu Zheng; Bin Zhu; Yutian Liu; Yi Fu; Jianyou Shi; Wu Tang (Chemical Engineering Journal, 2025)

Optimizing Vegetation and Building Configurations for Streetscape Heat Mitigation: A Multi-Scale Analysis under Extreme Heat - Wenjuan Ma; Zhaowu Yu; Wenjun Yang; Yujia Zhang; Yuxia Hu; Jinyu Hu; Huiwen Zhang; Gaoyuan Yang (Building and Environment, 2025)

Discoidin, CUB and LCCL domain containing 2 modulates angiogenesis by inhibiting VEGF receptor 2 endocytosis in endothelial cells - Xiaoning Liu; Shuai Wang; Qi Feng; Chao Yu; Wenjun Zhang; Chenyang Li; Weiwei Yang; Yanhong Zong; Lingling Guo; Runtao Wang; Lijing Li; Yunli Pei; et al. (Journal of Molecular Medicine, 2025)

Discrimination of tea varieties and bud sprouting phenology using UAV-based RGB and multispectral images - Litao Sun; Jiazhi Shen; Yilin Mao; Xiaojiang Li; Kai Fan; Wenjun Qian; Yu Wang; Caihong Bi; Hui Wang; Yang Xu; Jingbiao Xu; Zhaotang Ding (International Journal of Remote Sensing, 2025)

Associations of long-term exposure to PM2.5 and its constituents with children renal function: a national retrospective study in China - Siwen Yu; Chunxia Cui; Wei Wu; Lianlong Yu; Yiya Liu; Qijiong Zhu; Zhiqing Chen; Shangfeng Yang; Yi Lin; Jianxiong Hu; Guanhao He; Xiaomei Dong; et al. (Environmental Research, 2025)

Modification and mediation effects of ozone on heatwave-mortality association: A time series study in five provinces of China - Jianxiong Hu; Weiquan Zeng; Yanfang Guo; Ruilin Meng; Shaoli Huang; Chunliang Zhou; Yize Xiao; Min Yu; Biao Huang; Dalin Lu; Guanhao He; Wenjun Ma (Environmental Pollution, 2025)

Spatiotemporal Patterns of Human‐Perceived Temperature and Its Drivers Over the Rapid Urbanisation Area of China - Manjie Huang; Yanzhong Li; Aiqing Feng; Haiwen Yan; Wenjun Yu; Yintong Guo; Kunxia Yu (International Journal of Climatology, 2025)
Recent years have witnessed a significant rise in heat stress, including human‐perceived temperature (HPT), which has led to increased incidents of heat stroke and even fatalities, raising considerable concern about the risk to human settlement environments. However, the spatiotemporal pattern of HPT and the potential drivers related to climate and urbanisation remain unclear. This study focuses on the Yangtze River Delta region of China, a typical heat stress‐sensitive area, to examine the spatiotemporal dynamics of HPT using six commonly used indices: indoor apparent temperature (AT in ), outdoor shaded apparent temperature (AT out ), discomfort index (DI), effective temperature (ET), heat index (HI) and wet‐bulb temperature (WBT). Our analysis indicates a significant upward trend ( p out and WBT represent the most and least warming indices, respectively. Trends in HPT indices show significant regional variations. Over half of the cities analysed (56%) demonstrate positive urban–rural temperature differentials across all indices, with the most pronounced warming occurring in humid regions. The increase in anthropogenic heat emissions primarily drives HPT in the relatively arid regions in the northern and eastern areas. In contrast, decreasing vegetation cover contributes to changes in the southwestern, more humid area. Our findings can provide theoretical support for improving urban thermal environment management and developing mitigation strategies for human health.

Quinoa greens as a novel plant food: a review of its nutritional composition, functional activities, and food applications - Huange Huang; Qiang Wang; Jianxin Tan; Chunxiang Zeng; Junying Wang; Jingwei Huang; Yichen Hu; Qi Wu; Xiaoyong Wu; Changying Liu; Xueling Ye; Yu Fan; et al. (Critical Reviews in Food Science and Nutrition, 2025)

Corrigendum to “What drives the cooling dynamics of urban vegetation via evapotranspiration and shading under extreme heat?” [Sustainable Cities and Society, Volume 130 (2025) 106659] - Wenjuan Ma; Zhaowu Yu; Jiaqi Chen; Wenjun Yang; Yujia Zhang; Yuxia Hu; Mingchuan Shao; Jinyu Hu; Yiming Zhang; Huiwen Zhang; Gaoyuan Yang (Sustainable Cities and Society, 2025)

What drives the cooling dynamics of urban vegetation via evapotranspiration and shading under extreme heat? - Wenjuan Ma; Zhaowu Yu; Jiaqi Chen; Wenjun Yang; Yujia Zhang; Yuxia Hu; Mingchuan Shao; Jinyu Hu; Yiming Zhang; Huiwen Zhang; Gaoyuan Yang (Sustainable Cities and Society, 2025)

Probabilistic evaluation of enterprises' fraudulent report in pollutant levels based on machine learning: a case of hazardous waste generation quantity - Wen Fang; Qingyuan Yu; Wenjun Xie; Jianxun Yang; Zongwei Ma; Miaomiao Liu; Jun Bi (Resources, Conservation and Recycling, 2025)

The cell death-inducing protein BcPlp1 from Botrytis cinerea contributes to pathogenicity and modulates plant resistance - Xiaofei Nie; Ziyao Wang; Binbin Huang; Qiongnan Gu; Ran Xu; Shuang Yu; Chao Xiong; Zhiguo Liu; Wei Wei; Kai Bi; Wenjun Zhu (Plant Science, 2025)

Insights into the effects of different oxidants on TPHs removal and indigenous microbial communities in artificially contaminated soil - Wenjun XIE; Lichang ZHANG; Lei XU; Weiming LI; Yinglu TAO; Cailing SHI; Chufei YU; Xiuxiu YAN (Pedosphere, 2025)

Efficient disinfection of real toilet blackwater by ultraviolet/peracetic acid process: Selective intracellular biomolecular oxidation - Wenjun Yin; Jiabin Chen; Yue Xu; Chengzhi Yu; Xuefei Zhou; Yalei Zhang (Journal of Hazardous Materials, 2025)

Evolution of silicate weathering in the Yangtze River Basin since 3.5 Ma as archived in the East China Seas: Controlling factors and global significance - Jin Zhang; Shiming Wan; Peter D. Clift; Hualong Jin; Zehua Song; Yi Tang; Zhaojie Yu; Kaidi Zhang; Jian Lu; Wenjun Jiao; Anchun Li (Global and Planetary Change, 2025)

Euglena gracilis fermentation and kinetic scaleup using ethanol as substrate for β-1,3-glucan paramylon production - Lu Li; Pengsen Zhao; Jiang Yu; Yongqiang Wang; Wenjun Zhou; Lin Chen; Zhaohui Zhang; Tianzhong Liu; Xuefeng Lu (Chemical Engineering Journal, 2025)

Transients analysis of the offshore fixed multi-purpose integrated all-natural-cycle small lead-cooled reactor with the FRTAC code - Zinan Huang; Yuxing Liu; Song Li; You-Peng Zhang; Lu Meng; Yunxiang Li; Wenjun Hu; Yang Yu; Xing-Kang Su; Lu Zhang (Annals of Nuclear Energy, 2025)

A genomic compendium of cultivated food-derived lactic acid bacteria unveils their contributions to human health - Hao Jin; Keyu Quan; Lijun You; Lai-Yu Kwok; Teng Ma; Yalin Li; Xuan Shi; Xin Su; Ruirui Lv; Zhihong Sun; Wenjun Liu; Heping Zhang (Science Bulletin, 2025)

Effects of polyethylene microplastics on cadmium accumulation in Solanum nigrum L.: A study involving microbial communities and metabolomics profiles - Lei Xu; Chufei Yu; Wenjun Xie; Xiaosa Liang; Jie Zhan; Huiping Dai; Lidia Skuza; Jingru Xu; Yunqing Jing; Qingjian Zhang; Cailing Shi; Yinglu Tao; et al. (Journal of Hazardous Materials, 2025)

Long-term characteristics of formaldehyde concentrations in four Chinese residences and estimation of annual average - Jin Ye; Zhiyuan Wang; Tao Yu; Wenbin Zhuang; Wenqing Lai; Lei Tian; Wenjun Leng; Ying Song; Shaodan Huang; Yinping Zhang; Cong Liu; Bencheng Lin (Building and Environment, 2025)

Distinct Westerly Wind Burst Features in Cyclic and Noncyclic El Niño Events and Their Association with Western-Central Pacific SST Anomalies - Yu Liu; Wenjun Zhang; Zhuolin Xuan; Feng Jiang; Suqiong Hu (Advances in Atmospheric Sciences, 2025)

Towards Hazard Analysis Result Verification for Autonomous Ships: A Formal Verification Method Based on Timed Automata - Xiang-Yu Zhou; Shiqi Jin; Yang Mei; Xu Sun; Xue Yang; Shengzheng Nie; Wenjun Zhang (Journal of Marine Science and Engineering, 2025)
Enhancing the safety standards of autonomous ships is a shared objective of all stakeholders involved in the maritime industry. Since the existing hazard analysis work for autonomous ships often exhibits a degree of subjectivity, in the absence of data support, the verification of hazard analysis results has become increasingly challenging. In this study, a formal verification method in a risk-based assessment framework is proposed to verify the hazard analysis results for autonomous ships. To satisfy the characteristics of high time sensitivity, time automata are adopted as a formal language while model checking based on the formal verification tool UPPAAL is used to complete the automatic verification of the liveness of system modeling and correctness of hazard analysis results derived from extended System-Theoretic Process Analysis (STPA) by traversing the finite state space of the system. The effectiveness of the proposed method is demonstrated through a case study involving a remotely controlled ship. The results indicate that the timed automata network model for remotely controlled ships, based on the control structure, has no deadlocks and operates correctly, which demonstrates its practicability and effectiveness. By leveraging the verification of risk analysis results based on model checking, the framework enhances the precision and traceability of these inputs into RBAT. The results disclose the significance of the collaborative work between safety and system engineering in the development of autonomous systems under the definition of human–computer interaction mode transformation. These findings also hold reference value for other intelligent systems with potential hazards.

A framework to assess the operational state of autonomous ships with multi-component degrading systems - Xiang-Yu Zhou; Shiqi Jin; Xiaohang Ren; Xu Sun; Xiangkun Meng; Shengzheng Nie; Wenjun Zhang (Ocean Engineering, 2025)

Thermal coupled carbon nanotubes activated peroxymonosulfate for catalytic degradation of metronidazole and its application for membrane fouling mitigation - Kemeng Du; Wenjun Wu; Yufei Wang; Ruiyuan Jia; Yuru Liu; Xiaomeng Yu; Wenhui Wang; Guangshuo Yin; Jin Guo (Journal of Water Process Engineering, 2025)

Protection of lipase by self-assembled microgels under high-pressure - Yu Cheng; Lulu Liu; Can Zhao; Xiaolin Sun; Wenjun Li; Xingbin Yang; Zhong Zhang (Journal of Food Engineering, 2025)

Improvement of near-infrared spectroscopic assessment methods for the quality of Keemun black tea: Utilizing transfer learning - Yurong Chen; Junhan Wang; Jingfei Shen; Yifan Zuo; Qianfeng Yang; Yongning Wei; Jichen Wang; Qing Yu; Wenjun Lv; Luqing Li (Food Research International, 2025)

Metformin-induced precise targeted inhibition of ischemic neuronal death by a programable endogenous ROS-responsive nanoprodrug - Xiaofeng Tan; Ying Li; Hao Jin; Yu Zhou; Wenjun Li; Yun Zhao; Jun Hai; Jinyao Li; Zhongxiong Fan; Lichao Yang (Chemical Engineering Journal, 2025)

Trace copper doped LaMnO3 perovskite for PMS activation via electron transfer process towards pollutant elimination - Qianyi Wang; Wan Yu; Wenjun Xu; Zhen Li; Xiren Xia; Yin Xu (Journal of Water Process Engineering, 2025)

Implications of the different submerged extent of typical sandbars to local DOM and SDOM during the pre-flood season in the middle reaches of Yangtze River - Haoyang Shi; Hui Guo; Wenjun Yang; Chengcheng Bao; Xinxin Zhu; Sheng Bi; Yu Hu; Ting Li (Journal of Environmental Management, 2025)

Future climate change facilitates the herb drought-tolerant species distribution than woody species - Huimin Duan; Shuxia Sun; Wenjun Yang; Linqian Yu; Qun Gao; Hui Wang; Renqing Wang; Peiming Zheng (Environmental Research, 2025)

Synthesis of porous CNS@C@NC concave cubic nanobox composite as cathode material for aluminum batteries - Wenbin Luo; Jian Li; Yi Yu; Wenwei Su; Zetong Ren; Bo Niu; Zisheng Chao; JinCheng Fan; Wenjun Yi (Chemical Engineering Journal, 2025)

Advancements and perspectives of novel freezing and thawing technologies effects on meat: A review - Ling Jiang; Donghong Liu; Wenjun Wang; Ruiling Lv; Songfeng Yu; Jianwei Zhou (Food Research International, 2025)

Diversity analysis and function prediction of lactic acid bacteria in natural fermented dairy products in Mongolia - Xin Su; Zhixin Zhao; Ganpurev Dulamsuren; Yinsuo Liang; Lixia Zhao; Yu Li; Bilige Menghe; Wenjun Liu (Food Bioscience, 2025)

An improved local coarsening method for discrete element simulation on cracking propagation in rock and rock-like materials - Guansheng Han; Shaoqi Wang; Yu Zhou; Bo Li; Wenjun Lv; Weiqiang Chen; Qiongqiong Tang (Computers and Geotechnics, 2025)

Buchwald-Hartwig cross coupling constructs a p-type polymer with extended π-conjugated structure for high-performance Li-based dual-ion full batteries - Yang Gu; Wenjun Li; Yu Zheng; Bin Zhu; Jianyou Shi; Wu Tang (Chemical Engineering Journal, 2025)

Room-temperature CO2-to-carbon conversion facilitated by copper-gallium liquid metal - Xiao Chen; Jiacheng Liu; Qing Wang; Mengmeng Fu; Yunlong Li; Jialun He; Wenjun Zhan; Litian Liu; Danfeng Jiang; Yingguo Li; Chao Yu (Chemical Engineering Journal, 2025)

Orally administered metal–organic framework nanocubes for sequence-targeted quercetin delivery in colitis alleviation - Runan Zhao; Tao Chen; Shumeng Hu; Xuesong Chi; Songfeng Yu; Yanfei Li; Wenjun Wang; Beiwei Zhu; Donghong Liu; Jiangning Hu (Chemical Engineering Journal, 2025)

Inhibition of soluble epoxide hydrolase ameliorates cerebral blood flow autoregulation and cognition in alzheimer's disease and diabetes-related dementia rat models - Chengyun Tang; Jane J. Border; Huawei Zhang; Andrew Gregory; Shan Bai; Xing Fang; Yedan Liu; Shaoxun Wang; Sung Hee Hwang; Wenjun Gao; Gilbert C. Morgan; Jhania Smith; et al. (GeroScience, 2025)

The photo-based treatment technology simultaneously removes resistant bacteria and resistant genes from wastewater - Zicong Guo; Xiang Tang; Wenjun Wang; Zhangxiong Luo; Yuxi Zeng; Nan Zhou; Zhigang Yu; Dongbo Wang; Biao Song; Chengyun Zhou; Weiping Xiong (Journal of Environmental Sciences, 2025)

Interlayer-engineered “six-in-one” nanozymes for cascade enzymatic/photothermal oncotherapy - Zhenli Zhou; Danyang Li; Linke Yu; Yaoyao Zhu; Shuqing He; Luyang Wang; Li Yan; Wenjun Zhang; Lei Li; Enna Ha; Junqing Hu (Chemical Engineering Journal, 2025)

Reverse Size Effect of the Unconfined Compressive Strength of Crystalline Rock: A Grain-Scale Perspective - Qinyuan Liang; Hengxing Lan; Yu Zhou; Bo Li; Weifeng Sun; Shijie Liu; Wenjun Lv (Rock Mechanics and Rock Engineering, 2025)

Effects of fine particulate matter bound heavy metals on intentional self-harm deaths in Guangzhou, China, insight from core chemical constituents - Chunyan Gui; Han Zhang; Zhanlu Lv; Tao Liu; Shengbing Yu; Yanjun Xu; Hualiang Lin; Jianpeng Xiao; Wenjun Ma; Bin Luo; Ling-Chuan Guo (International Journal of Biometeorology, 2025)

Increasing human-perceived temperature exacerbated by urbanization in China's major cities: Spatiotemporal trends and associated driving factors - Haiwen Yan; Yanzhong Li; Yincong Xing; Xiaobing Chen; Xiaojun Guo; Yixing Yin; Wenjun Yu; Manjie Huang; Jiacheng Zhuang (Sustainable Cities and Society, 2025)

Historical inventories and future scenarios of multiple hazardous air pollutants (HAPs) emissions from the iron and steel production industry in China - Junqi Yang; Hezhong Tian; Zhiqiang Fu; Xiaoxuan Bai; Kun Wang; Wenjun Liu; Yiping Lu; Yu Zhou; Hongyan Zhao; Jiangyu Cui; Qinwei Du (Science of The Total Environment, 2025)

A realistic 3D grain-based modeling approach for reproducing the mechanical and failure behavior of brittle granites - Yu Zhou; Wenjun Lv; Bo Li; Qinyuan Liang; Shaoqi Wang (International Journal of Rock Mechanics and Mining Sciences, 2025)

Tea polyphenols coating improves physiological properties, microstructure and chemical composition of cuticle to suppress quality deterioration of passion fruit during cold storage - Yu Wang; Wenjun Jia; Xin Wang; Muhammad Muzammal Aslam; Wen Li; Yuanzhi Shao (Food Chemistry, 2025)

Association of residential greenness exposures on disability: Findings from the cohort study on global AGEing and Adult Health (SAGE) in China - Zhiqing Chen; Yan Shi; Yanfei Guo; Siwen Yu; Qijiong Zhu; Shangfeng Yang; Yuan Zheng; Yayi Li; Yixiang Huang; Wan Peng; Guanhao He; Jianxiong Hu; et al. (Environmental Research, 2025)

Experimental study on regular wave breakage and nonlinear characteristics on the terrain of steep coral islands and reefs - Wei Li; Tingqiu Li; Min Yu; Xuyi Fang; Cong Liu; Wenjun Zhou (Natural Hazards, 2025)

Seepage field and drainage system in the connection part of underwater tunnel based on conformal mapping method - Helin Fu; Kaixun Hu; Yimin Wu; Yong Yu; Wenjun Liu (Tunnelling and Underground Space Technology, 2024)

Bioaccumulation mechanisms of perfluoroalkyl substances (PFASs) in aquatic environments: Theoretical and experimental insights - Jianbo Hu; Xu Yang; Xianyu Song; Yongtao Miao; Yuanhong Yu; Wenjun Xiang; Meiying Huang; Weirong Wu; Kezhong Liang; Shuangliang Zhao; Honglai Liu (Journal of Hazardous Materials, 2024)

Investigating the potential risk of cadmium exposure on seizure severity and anxiety-like behaviors through the ferroptosis pathway in epileptic mice: An integrated multi-omics approach - Yuanjin Chang; Xiaofan Jiang; Jianrui Dou; Ruijin Xie; Wenjing Zhao; Yingsi Cao; Ju Gao; Fanglong Yao; Dongqin Wu; Huiya Mei; Yanqi Zhong; YuXi Ge; et al. (Journal of Hazardous Materials, 2024)

Biofiltration for low-carbon rural wastewater treatment: A review of advancements and opportunities towards carbon neutrality - Guangyi Ma; Zheming Xi; Yiheng Chen; Wenjie Xu; Chengde Sun; Wenjun Zhuang; Tao Zhang; Dapeng Li; Yang Pan; Yu-You Li; Zhe Kong (Journal of Environmental Chemical Engineering, 2024)

Ionic titanium is expected to improve the nutritional quality of Tartary buckwheat sprouts through flavonoids and amino acid metabolism - Hang Yuan; Qiang Wang; Jianxin Tan; Jingyu Wu; Chenggang Liang; Yan Wang; Tingting Deng; Zhiming Hu; Changying Liu; Xueling Ye; Qi Wu; Xiaoyong Wu; et al. (Food Chemistry, 2024)

Culturomics: A promising approach for exploring bacterial diversity in natural fermented milk - Yu Li; Xiaoqing Guo; Qingting Peng; Tingting Shen; Jianxia Yao; Yue Wei; Haiting Duan; Wenjun Liu (Food Bioscience, 2024)

Depressed root morphology and altered hormone signaling in Toona sinensis brought about by different forms of excessive nitrogen - Xiaochi Yu; Fei Yi; Xiaoxi Wang; Bingyang Liu; Yue Fei; Peng Zhang; Junhui Wang; Wenjun Ma (Trees, 2024)

Development and evaluation of suitable reference genes for qRT-PCR normalization of hybrids derived from Lycium barbarum and Lycium ruthenicum - Yu Liu; Wenjun Shi; Defang Zhang (Molecular Biology Reports, 2024)

Diversifying the benzenesulfonamide scaffold for potential V-ATPase inhibitors: synthesis and insecticidal activity evaluation - Hao Qian; Tao Guo; Jinyu Zhang; Yingkun Hu; Changzhao Wang; Keyin Yu; Wenjun Wu; Jiwen Zhang (Molecular Diversity, 2024)

High-yield magnetosome production of Magnetospirillum magneticum strain AMB-1 in flask fermentation through simplified processing and optimized iron supplementation - Yu Wang; Zhengyi Liu; Wenjun Li; Hongli Cui; Yandi Huang; Song Qin (Biotechnology Letters, 2024)

Effect of antibiotic perturbation on nitrous oxide emissions: An in-depth analysis - Wenjun Yu; Kashif Hayat; Junwei Ma; Xiaoping Fan; Yuyi Yang; Zulin Zhang; Qiaogang Yu; Mingrong Qian; Hui Lin (Critical Reviews in Environmental Science and Technology, 2024)

From challenge to opportunity: Revolutionizing the monitoring of emerging contaminants in water with advanced sensors - Peng Chen; Jingquan Wang; Yanei Xue; Chunmiao Wang; Wenjun Sun; Jianwei Yu; Hongguang Guo (Water Research, 2024)

Breaking boundaries in slag waste heat recovery: Review and future perspective of dry centrifugal granulation technology - Wenjun Duan; Rongmin Li; Zhimei Wang; Junxiang Liu; Jingyao Ji; Jiaxu Liu; Qingbo Yu (Process Safety and Environmental Protection, 2024)

Enhanced effect of electric field on methane pyrolysis and hydrogen production by Ni-Supported MoS2 Catalyst: A molecular dynamics study - Wenjun Zhou; Yu Zhang; Muhammad Sajjad Ahmad; Boxiong Shen; Sibudjing Kawi (Fuel, 2024)

Effect of partial substitution of NaCl by KCl on aggregation behavior and gel properties of beef myosin - Chuanlong Yu; Lingli Chen; Kehui Ouyang; Hui Chen; Mingsheng Xu; Suyun Lin; Wenjun Wang (Food Chemistry, 2024)

Oncogenic miRNAs dependent photothermal-immunotherapy enhanced by on-demand manipulation of immunosuppressive microenvironment using engineered gold nanoparticles for effective treatment of primary and metastatic tumor - Li Chen; Yu Hu; Wenyun Mu; Tao Liu; Wenjun Tang; Lin Weng; Yanmin Zhang; Xin Chen (Chemical Engineering Journal, 2024)

Light footprint of microalgae cultivation system addressed by modified Cornet model - Lu Li; Yongqiang Wang; Wenjun Zhou; Zhifei Yu; Guodong Luan; Lin Chen; Tianzhong Liu; Xuefeng Lu (Bioresource Technology, 2024)

Oxaliplatin lipidated prodrug synergistically enhances the anti-colorectal cancer effect of IL12 mRNA - Hui Liu; Yating Du; Desheng Zhan; Wenjun Yu; Yan Li; Aiping Wang; Jianpeng Yin; Haiqiang Cao; Yuanlei Fu (Drug Delivery and Translational Research, 2024)

Analyzing risk influencing factors of ship collision accidents: A data-driven Bayesian network model integrating physical knowledge - Xiangkun Meng; Hongqiang Li; Wenjun Zhang; Xiang-Yu Zhou; Xue Yang (Ocean & Coastal Management, 2024)

Analyzing ship collision accidents in China: A framework based on the N-K model and Bayesian networks - Xiangkun Meng; Hongqiang Li; Wenjun Zhang; Xiang-Yu Zhou; Xue Yang (Ocean Engineering, 2024)

Lactobacillus plantarum P9 ameliorates dysfunctional immune and metabolic homeostasis along the gut–liver axis in a nonalcoholic fatty liver disease with low-grade colitis mouse model - Yang Zhan; Qiong Li; Tao Li; Qinqin Yu; Yingmeng Li; Xiaoying Cheng; Yong Sun; Xiaoya Wang; Fanghua Guo; Hua Zhang; Wenjun Liu (Food Bioscience, 2024)

Borehole lithology modelling with scarce labels by deep transductive learning - Jichen Wang; Jing Li; Kun Li; Zerui Li; Yu Kang; Ji Chang; Wenjun Lv (Computers & Geosciences, 2024)

Magneto-elastic for wireless intraocular pressure monitoring - Yu Lin; Shengxin Xiang; Wenjun Zou; Xiaohua Chen; Feixiang Gao; Yi Liu; Yijie Sun; Ping Chen; Quanxi Zhang; Xuelian Han; Baoping Wang; Yong Yao; et al. (Chemical Engineering Journal, 2024)

Deep mineralization of bisphenol A via Cu–Mn spinel oxide nanospheres anchored N-doped carbon activated peroxymonosulfate - Xiaobo Wang; Lin He; Yu Zhou; Nan Wang; Lihua Zhu; JunTao Yan; Deng Ding; Wenjun Zhu; Xiaohua Zuo; Jinpeng Wang; Xiaoyong Wu (Chemical Engineering Journal, 2024)

Transcriptomic Analysis Provides Insights into the Energetic Metabolism and Immune Responses in Litopenaeus vannamei Challenged by Photobacterium damselae subsp. damselae - Libao Wang; Qiuwen Xu; Zhijun Yu; Zhenxin Hu; Hui Li; Wenjun Shi; Xihe Wan (Fishes, 2024)
To explore the molecular mechanisms of the Litopenaeus vannamei response to infection by Photobacterium damselae, reveal its immune response and energetic metabolic effect, and provide a valuable genetic data source for the scientific prevention and control of Vibrio infection, transcriptomic analysis, RT-qPCR, and physiological and biochemical tests were conducted. The results showed that the expression of key genes involved in lipid and carbohydrate transport, such as apolipoprotein and TPS, was upregulated after pathogenic infection, which brought the accumulation of triacylglycerol and trehalose into the hemolymph. Additionally, the pathogenic infection selectively triggered an immune response in infected L. vannamei, activating certain immune pathways, such as the serpins and MAPK pathways. The pathogenic infection suppressed the activity of phenoloxidase (PO), and the prophenoloxidase (PPO) cascade responses were suppressed by the invasive bacteria. This paper will help us understand the energetic metabolism, immune response, and activation of the immune recognition response after pathogenic infection by P. damselae, and it lays a theoretical foundation for the biological prevention and control of P. damselae infection.

Optimizing sustainability and profitability: A multi-step approach to the synthesis of X-zeolite from blast furnace slag - Wenjun Duan; Rongmin Li; Zhimei Wang; Jingyao Ji; Jiaxu Liu; Qingbo Yu (Process Safety and Environmental Protection, 2024)

Unveiling the promotional performance of CO oxidation over Na-doped Pt-0.5P&W/TiO2 catalyst: “SMSI” effect of Na in catalysis - Junda He; Jian Li; Wenjun Liang; Liyun Song; Jinyu Yuan; Jianyu Cai; Zehui Yu (Fuel, 2024)

Aloe vera and tea polyphenols composite coating delays passion fruit senescence by promoting phenolic and flavonoid accumulation - Yu Wang; Muhammad Muzammal Aslam; Xin Wang; Hui Gu; Wenjun jia; Wen Li; Yuanzhi Shao (Food Research International, 2024)

Biocompatible hydrophobic cross-linked cyclodextrin-based metal-organic framework as quercetin nanocarrier for enhancing stability and controlled release - Runan Zhao; Tao Chen; Yanfei Li; Lihang Chen; Yu Xu; Xuesong Chi; Songfeng Yu; Wenjun Wang; Donghong Liu; Beiwei Zhu; Jiangning Hu (Food Chemistry, 2024)

Effect of urban street canyon aspect ratio on fire-induced air pollutants dispersion under cross wind - Shengzhong Zhao; Junhao Yu; Haoran Yang; Imad Obadi; Tiantian Xu; Fei Wang; Lin Xu; Wenjun Lei (Atmospheric Pollution Research, 2024)

Pt-promoted mesoporous Beta zeolite catalysts for n-Hexane isomerization with enhanced selectivity to dibranched isomers - Pengzhao Wang; Tingting Chen; Zihui Qiu; Wenjun Yao; Pengpeng Liu; Yongze Zhang; Yu Song; Qingyan Cui; Xiaojun Bao (Fuel, 2024)

H2O2 self-supplied CuFeOx nanosystem as fenton-like reaction agents for endogenous/exogenous responsive synergetic antibacterial therapy - Lei Zhao; Yawen Chen; Qinglin Wei; Xinyi Lv; Ying Cui; Wenjun Wang; Xiaozhou Mou; Xuejiao Song; Xiaochen Dong; Yu Cai (Chemical Engineering Journal, 2024)

MLP-based multimodal tomato detection in complex scenarios: Insights from task-specific analysis of feature fusion architectures - Wenjun Chen; Yuan Rao; Fengyi Wang; Yu Zhang; Tan Wang; Xiu Jin; Wenhui Hou; Zhaohui Jiang; Wu Zhang (Computers and Electronics in Agriculture, 2024)

Do E-governance, mineral resources, and policy stringency facilitate economic growth in selected resource-rich countries - Wenjun Wu; Zhilong Zhao; Siming Yu; Minyuan Zhang (Resources Policy, 2024)

History of human activity in South China since 7 cal ka BP: Evidence from a sediment record in the South China Sea - Mengshan Ju; Shiming Wan; Peter D. Clift; Wenqiang Pei; Dongfeng Jiao; Jin Zhang; Wenjun Jiao; Debo Zhao; Zhaojie Yu; Zehua Song; Anchun Li (Quaternary Science Reviews, 2024)

Lipoic acid/trometamol assembled hydrogel as injectable bandage for hypoxic wound healing at high altitude - Rui Lei; Mingbao Gu; Jinyan Li; Wenjun Wang; Qian Yu; Rizwan Ali; Jiajia Pang; Meilun Zhai; Yang Wang; Kunxi Zhang; Jingbo Yin; Jinghong Xu (Chemical Engineering Journal, 2024)

Investigating the cooling effects of land cover and landscape patterns surrounding rivers: Insights from the subtropical city of Changsha, China - Jie Tan; Wenjun Kuang; De Yu; Weijun Zhou; Xigui Li; Qin Liu; Libo He (Urban Climate, 2024)

Preterm Birth Alters the Regional Development and Structural Covariance of Cerebellum at Term-Equivalent Age - Feifei Xu; Yu Wang; Wenjun Wang; Wenjia Liang; Yuchun Tang; Shuwei Liu (The Cerebellum, 2024)

Enhancing thermal comfort prediction in high-speed trains through machine learning and physiological signals integration - Wenjun Zhou; Mingzhi Yang; Xiaoyan Yu; Yong Peng; Chaojie Fan; Diya Xu; Qiang Xiao (Journal of Thermal Biology, 2024)

Changed evapotranspiration and its components induced by greening vegetation in the Three Rivers Source of the Tibetan Plateau - Jiacheng Zhuang; Yanzhong Li; Peng Bai; Li Chen; Xiaojun Guo; Yincong Xing; Aiqing Feng; Wenjun Yu; Manjie Huang (Journal of Hydrology, 2024)

Plasmonic array assisted mass spectrometry for preferential metabolite detection - Xvelian Li; Wei Chen; Mengyi Wu; Wenjun Yu; Mengfei Wang; Minjia Niu; Fanyu Meng; Yuewei Zhao; Ahmed Osman; Nahla O. Mousa; Hui Shi; Kun Qian; et al. (Chemical Engineering Journal, 2024)

Biomimetic hybrid porous microspheres with plant membrane-wall structure for evaluating multiscale mechanisms of ultrasound-assisted mass transfer - Jiaheng Li; Wenjun Wang; Weidong Xu; Songfeng Yu; Ruiling Lv; Jianwei Zhou; Donghong Liu (Chemical Engineering Journal, 2024)

Accumulation and composition characteristics of organic phosphorus in sediments from the Yangtze River–connected lakes, China - YanTing Yan; Dongzheng Liu; WenJun Zhong; Zhaokui Ni; Yu Li; Shengrui Wang (Journal of Soils and Sediments, 2024)

Circulating exosome-mediated AMPKα–SIRT1 pathway regulates lipid metabolism disorders in calf hepatocytes - Daoliang Zhang; Hongyan Ding; Chang Liu; Yingying Huang; Wenjun Tai; Shibin Feng; Xichun Wang; Chang Zhao; Yu Li (Research in Veterinary Science, 2024)

Variations of the fungal microbiome in Corydalis Rhizoma with different collection areas, processing methods, and storage conditions - Wenjun Jiang; Mengyue Guo; Jingsheng Yu; Chune Fan; Meihua Yang; Xiaohui Pang (Food Research International, 2024)

Simultaneous identification of a non-point contaminant source with Gaussian spatially distributed release and heterogeneous hydraulic conductivity in an aquifer using the LES-MDA method - Wenjun Zhang; Teng Xu; Zi Chen; J. Jaime Gómez-Hernández; Chunhui Lu; Jie Yang; Yu Ye; Miao Jing (Journal of Hydrology, 2024)

Modeling denitrification nitrogen losses in China's rice fields based on multiscale field‐experiment constraints - Huayan Zhang; Wulahati Adalibieke; Wenxin Ba; Klaus Butterbach‐Bahl; Longfei Yu; Andong Cai; Jin Fu; Haoming Yu; Wantong Zhang; Weichen Huang; Yiwei Jian; Wenjun Jiang; et al. (Global Change Biology, 2024)
Denitrification plays a critical role in soil nitrogen (N) cycling, affecting N availability in agroecosystems. However, the challenges in direct measurement of denitrification products (NO, N 2 O, and N 2 ) hinder our understanding of denitrification N losses patterns across the spatial scale. To address this gap, we constructed a data‐model fusion method to map the county‐scale denitrification N losses from China's rice fields over the past decade. The estimated denitrification N losses as a percentage of N application from 2009 to 2018 were 11.8 ± 4.0% for single rice, 12.4 ± 3.7% for early rice, and 11.6 ± 3.1% for late rice. The model results showed that the spatial heterogeneity of denitrification N losses is primarily driven by edaphic and climatic factors rather than by management practices. In particular, diffusion and production rates emerged as key contributors to the variation of denitrification N losses. These findings humanize a 38.9 ± 4.8 kg N ha −1 N loss by denitrification and challenge the common hypothesis that substrate availability drives the pattern of N losses by denitrification in rice fields.

Study on engineering geological characteristics of southwest shale oil based on nuclear magnetic resonance imbibition flooding technology - Liang Wang; Fan Yu; Jiqing Shi; Junliang Peng; Wenjun Zhao; Yuntao Liu; Jun Yan (Acta Geophysica, 2024)

The joint associations of ambient air pollutants and weather factors with mortality: Evidence from a national time-stratified case-crossover study in China - Qijiong Zhu; Min Yu; Guoxia Bai; Chunliang Zhou; Ruilin Meng; Biao Huang; Weiwei Gong; Haoming Zhang; Ruying Hu; Zhulin Hou; Yize Xiao; Donghui Jin; et al. (Science of The Total Environment, 2024)

A novel low sampling rate and cost-efficient active sampler for medium/long-term monitoring of gaseous pollutants - Zhiyuan Wang; Tao Yu; Jin Ye; Lei Tian; Bencheng Lin; Wenjun Leng; Cong Liu (Journal of Hazardous Materials, 2024)

Source, type, controlling, and utilization of by-and side-products arising from the production process of 2-acrylamido-2-methyl propane sulfonic acid (AMPS): A review - Shaohua Li; Wenjun Long; Zhongjin Wei; Yu Zhao; Xiaori Sun; Fengshan Zhou (Journal of Cleaner Production, 2024)

Environment-triggered nanoagent with programmed gas release performance for accelerating diabetic infected wound healing - Yan Xu; Jingai Jiang; Xinyi Lv; Hui Li; Dongliang Yang; Wenjun Wang; Yanling Hu; Longcai Liu; Xiaochen Dong; Yu Cai (Chemical Engineering Journal, 2024)

Determination of uptake rates of volatile organic compounds by 24-hour passive sampling and their application in enclosed ship cabin environments - Tao Yu; Yan Wang; Longfei Chen; Wenjun Leng; Yue Shi; Bencheng Lin; Juntao Zhao; Zhiyuan Wang; Jinhan Mo; Cong Liu (Building and Environment, 2024)

Integrated metabolomic and transcriptomic analyses reveal the molecular mechanism of amino acid transport between source and sink during tea shoot development - Jie Zhang; Kangwei Sun; Yu Wang; Wenjun Qian; Litao Sun; Jiazhi Shen; Zhaotang Ding; Kai Fan (Plant Cell Reports, 2024)

Comparing univariate filtration preceding and succeeding PLS-DA analysis on the differential variables/metabolites identified from untargeted LC-MS metabolomics data - Suyun Xu; Caihong Bai; Yanli Chen; Lingling Yu; Wenjun Wu; Kaifeng Hu (Analytica Chimica Acta, 2024)

The comparison of mortality burden between exposure to dry-cold events and wet-cold events: A nationwide study in China - Muyun Li; Wen Fang; Ruilin Meng; Jianxiong Hu; Guanhao He; Zhulin Hou; Maigeng Zhou; Chunliang Zhou; Sui Zhu; Yize Xiao; Min Yu; Biao Huang; et al. (Science of The Total Environment, 2023)

The association of heatwave with drowning mortality in five provinces of China - Zhongguo Huang; Zhixing Li; Jianxiong Hu; Sui Zhu; Weiwei Gong; Chunliang Zhou; Ruilin Meng; Xiaomei Dong; Min Yu; Xiaojun Xu; Lifeng Lin; Jianpeng Xiao; et al. (Science of The Total Environment, 2023)

Dynamical modeling the effect of glucagon-like peptide on glucose–insulin regulatory system based on mice experimental observation - Yu Zhao; Wenjun Jing; Liping Li; Shi Zhao; Masayuki Yamasaki (Mathematical Biosciences, 2023)

Anaerobic biodegradation of azo dye reactive black 5 by a novel strain Shewanella sp. SR1: Pathway and mechanisms - Jiale Liu; Lu Fan; Wenjun Yin; Shusheng Zhang; Xiaomei Su; Hongjun Lin; Haiying Yu; Zhenghai Jiang; Faqian Sun (Journal of Environmental Management, 2023)

Fractional model for simulating Long-Term fracture conductivity decay of shale gas and its influences on the well production - Yu Peng; Ang Luo; Yongming Li; Yijia Wu; Wenjun Xu; Kamy Sepehrnoori (Fuel, 2023)

The Research Progress and Prospects of the NIGT1.2 Gene in Plants - Qiang Lv; Wenjun Ji; Hao Chu; Mingtong You; Weiwei Tang; Min Chen; Yu Huang; Paul Promise Michael; Bo Zhou; Fenghua Wang; Dan Peng (Journal of Plant Growth Regulation, 2023)

Genesis of the newly discovered Pb–Zn vein of the Sucha giant fluorite deposit in Inner Mongolia: Constraints from LA-ICP-MS trace element of pyrite and sphalerite - Biao Jiang; Denghong Wang; Xiulang Pu; Yu Liu; Yuchuan Chen; Wenjun Wang; Wenwen Ma; Chengliang Wang; Qiang Wang; Wei Chen (Applied Geochemistry, 2023)

A Domain-Based Model for Identifying Regional Collision Risk and Depicting Its Geographical Distribution - Zihao Liu; Zhaolin Wu; Zhongyi Zheng; Xianda Yu; Xiaoxuan Bu; Wenjun Zhang (Journal of Marine Science and Engineering, 2023)
In recent years, the increasing volume and complexity of ship traffic has raised the probability of collision accidents in ports, waterways, and coastal waters. Due to the relative rarity of collision accidents, near misses have been used in the research to study the collision risk in the relevant water areas. However, the factor of near miss identification is usually limited to the relative distance between ships, and the instantaneous quantification and geographical distribution of collision risk is not paid enough attention. Therefore, this article proposed a domain-based regional collision risk model that can quantify the collision risk by detecting near miss scenarios. The proposed model is capable of quantifying the collision risk in the water area instantaneously and periodically and can be used to depict the geographical distribution of collision risks in combination with a grid method and the spatial interpolation technique. To validate the proposed model, some experimental case studies were carried out using automatic identification system (AIS) data from the Bohai Strait. The results show the capability and advantage of the proposed model in regional collision risk identification and visualization, which is helpful for maritime surveillance when monitoring and organizing ship traffic and may therefore contribute to the improvement of maritime safety.

Intraspecific microdiversity and ecological drivers of lactic acid bacteria in naturally fermented milk ecosystem - Lijun You; Hao Jin; Lai-Yu Kwok; Ruirui Lv; Zhixin Zhao; Menghe Bilige; Zhihong Sun; Wenjun Liu; Heping Zhang (Science Bulletin, 2023)

Efficient Removal of Pb(II), Cr(VI), and Tetracycline Hydrochloride from Aqueous Solutions Using UiO-66-AMP@PAN: Thermodynamics, Kinetics, and Isothermal Adsorption - Wenjun Qu; Huili Wang; Guodong Li; Zhaoping Song; Xiaona Liu; Fengshan Zhang; Wenxia Liu; Dehai Yu; Dandan Ji (Journal of Environmental Chemical Engineering, 2023)

Why does rangeland integration by transfer fail to overcome the tragedy of anticommons? - Lianhua Chasu; WenJun Li; Yu Mu (Ambio, 2023)

Associations of metal mixtures with thyroid function and potential interactions with iodine status: results from a cross-sectional study in MEWHC - Xiaoting Ge; Junxiu He; Sencai Lin; Yu Bao; Yuan Zheng; Hong Cheng; Haiqing Cai; Xiuming Feng; Wenjun Yang; Sihan Hu; Lin Wang; Qijing Liao; et al. (Environmental Science and Pollution Research, 2023)

Investigating real-time monitoring indices of compaction quality from particle movement characteristics of distinctly-graded unbound aggregate materials subjected to vibratory compaction - Wenjun Hua; Yuanjie Xiao; Qunding Yu; Meng Wang; Wenqi Li; Erol Tutumluer; Yuliang Chen; Zhiyong Li (Transportation Geotechnics, 2023)

CO2 sequestration and CaCO3 recovery with steel slag by a novel two-step leaching and carbonation method - Can Cheng; Wenjun Huang; Haomiao Xu; Zhisong Liu; Xianwei Li; Hongzhi Shi; Yongmei Yu; Zan Qu; Naiqiang Yan (Science of The Total Environment, 2023)

New insights into sulfur input induced methylmercury production and accumulation in paddy soil and rice - Yunyun Li; Nali Zhu; Wenjun Hu; Yu-rong Liu; Wen Jia; Guoming Lin; Hong Li; Yufeng Li; Yuxi Gao; Jiating Zhao (Journal of Hazardous Materials, 2023)

Facile engineering of metal–organic framework derived SnO2-ZnO composite based gas sensor toward superior acetone sensing performance - Hui Zhang; Shisong Guo; Wenjun Zheng; Haichao Wang; Hua-Yao Li; Mei-Hui Yu; Ze Chang; Xian-He Bu; Huan Liu (Chemical Engineering Journal, 2023)

Efficient decolorization of melanoidin in raw molasses wastewater by thermophilic esterase in actual extreme conditions - Zedong Zhang; Wanting Hu; Qiuyue Xie; Yuezhe Shi; Yutong Zhao; Yaxin Deng; Jiaxin He; Xia Wu; Yu Zhang; Wenqi Zhang; Pengjun Liu; Hao Yang; et al. (Bioresource Technology, 2023)

New failure criterion for rock slopes with intermittent joints based on energy mutation - Yu Zhou; Wenjun Lv; Zihan Zhou; Qiongqiong Tang; Guansheng Han; Jianshuai Hao; Weiqiang Chen; Faquan Wu (Natural Hazards, 2023)

Nitrogen deposition weakens the stimulatory effect of Moso bamboo (Phyllostachys edulis) leaf litter on soil CO2 emissions - Shoujia Zhuo; Youchao Chen; Haikuo Zhang; Wenting Jiang; Bo Fan; Yongfu Li; Bing Yu; Wenjun Li; Min Duan; Scott X. Chang; Yanjiang Cai (Journal of Soils and Sediments, 2023)

Quantifying seasonal ground deformation in Taiyuan basin, China, by Sentinel-1 InSAR time series analysis - Wei Tang; Xiangjun Zhao; Gang Bi; Mingjie Chen; Siyu Cheng; Mingsheng Liao; Wenjun Yu (Journal of Hydrology, 2023)

Conversion of endogenous phenolic acid in brown rice by bioextrusion of mesophilic α-amylase - Yu Qin; Shuohan Ma; Jianwei Zhou; Dandan Li; Jianle Chen; Wenjun Wang; Huan Cheng; Zhengzong Wu; Jinhu Tian; Enbo Xu; Donghong Liu (Food Bioscience, 2023)

Two–dimensional metal–organic framework nanosheets: An efficient two–electron oxygen reduction reaction electrocatalyst for boosting cathodic luminol electrochemiluminescence - Chulei Zhao; Chaoyun Ma; Fuping Zhang; Wenjun Li; Chenglin Hong; Yu Qi (Chemical Engineering Journal, 2023)

Evolution of Asian drying since 30 Ma revealed by clay minerals record in the West Pacific and its tectonic-climatic forcing - Yi Tang; Shiming Wan; Debo Zhao; Zhaojie Yu; Zhaokai Xu; Jin Zhang; Zehua Song; Mengjun Li; Hualong Jin; Wenjun Jiao; Hongkun Dong; Anchun Li (Science China Earth Sciences, 2023)

Research on the Marine Antifouling Ability and Mechanism of Acrylate Copolymers and Marine Coatings Based on a Synergistic Effect - Wenjun Zhou; Yu Zhou; Chunhua Ni; Liangmin Yu; Zhengjun Yuan; Changcheng Li; Xuefeng Yan (Journal of Ocean University of China, 2023)

Overexpression of ClWRKY48 from Cunninghamia lanceolata improves Arabidopsis phosphate uptake - Weiwei Tang; Jing Wang; Qiang Lv; Paul Promise Michael; Wenjun Ji; Min Chen; Yu Huang; Bo Zhou; Dan Peng (Planta, 2023)

Oxidative potential of heavy-metal contaminated soil reflects its ecological risk on earthworm - Chunmei Ran; Chunguang Liu; Chu Peng; Xinxin Li; Yu Liu; Ye Li; Wenjun Zhang; Hongming Cai; Lei Wang (Environmental Pollution, 2023)

Environmental fate and metabolism of the systemic triazolinthione fungicide prothioconazole in different aerobic soils - Xingyan Pang; Jiaoyang Li; Pengfei Xu; Wenjun Yang; Lei Huang; Sufen Zhang; Zhiyang Yu; Qingfu Ye (Journal of Hazardous Materials, 2023)

Emergence of lnu(C) variant conferring lincomycin resistance in Campylobacter coli of chicken origin - Wenjun Li; Dian Jiao; Jin Kang; Runhao Yu; Wenbo Zhao; Chunyan Xu; Ruichao Li; Xiang-Dang Du; Hong Yao (International Journal of Food Microbiology, 2023)

A three-dimensional active biochar for sintering in steel industry and remove methylene blue by synergistic activation of H3PO4 and ZnCl2 - Yu Zhang; Boxiong Shen; Muhammad Sajjad Ahmad; Wenjun Zhou; Rana Rehan Khalid; Muhammad Ibrahim; Awais Bokhari (Fuel, 2023)

Slip partitioning and crustal deformation patterns in the Tianshan orogenic belt derived from GPS measurements and their tectonic implications - Chuanyong Wu; Peizhen Zhang; Zhuqi Zhang; Wenjun Zheng; Binbin Xu; Weitao Wang; Zhongyuan Yu; Xunye Dai; Boxuan Zhang; Kezhi Zang (Earth-Science Reviews, 2023)

Relationship between potential waterway depth improvement and evolution of the Jingjiang Reach of the Yangtze River in China - Yunping Yang; Ming Li; Wanli Liu; Yuanfang Chai; Jie Zhang; Wenjun Yu (Journal of Geographical Sciences, 2023)

Prediction for odor gas generation from domestic waste based on machine learning - Yuanyan Jiang; Jiawei Huang; Wei Luo; Kejin Chen; Wenrou Yu; Wenjun Zhang; Chuan Huang; Junjun Yang; Yingzhou Huang (Waste Management, 2023)

Associations between serum polychlorinated biphenyls, halogen flame retardants, and renal function indexes in residents of an e-waste recycling area - Ling-Chuan Guo; Zhanlu Lv; Tingting Zhu; Guanhao He; Jianxiong Hu; Jianpeng Xiao; Tao Liu; Shengbing Yu; Jinliang Zhang; Han Zhang; Wenjun Ma (Science of The Total Environment, 2023)

Digestion, absorption, and transport properties of soy-fermented douchi hypoglycemic peptides VY and SFLLR under simulated gastrointestinal digestion and Caco-2 cell monolayers - Songfeng Yu; Wenjun Wang; Tingting Bu; Runan Zhao; Ruihao Niu; Ling Liu; Jiaheng Li; Jianping Wu; Donghong Liu (Food Research International, 2023)

Non-targeted cellular metabolomics revealing the metabolomic features and anti-tumor mechanisms of cyanidin-3-O-arabinoside on Caco-2 cells - Ge Xu; Wenjun Xue; Dan Zhang; Zhipeng Yu; Jingbo Liu; Wenzhu Zhao (Food Bioscience, 2023)

Development and application of a multiplex qPCR assay for the detection of duck circovirus, duck Tembusu virus, Muscovy duck reovirus, and new duck reovirus - Yan Wen Yin; Chenyong Xiong; Kai Chuang Shi; Shou Yu Xie; Feng Long; Jun Li; Min Zheng; Xian Kai Wei; Shuping Feng; Sujie Qu; Wenjun Lu; Hongjin Zhou; et al. (Virus Genes, 2023)

Whole-genome sequencing and comparative genomic analysis of a pathogenic Enterocytozoon hepatopenaei strain isolated from Litopenaeus vannamei - Libao Wang; Hui Li; Wenjun Shi; Yi Qiao; Pan Wang; Zhijun Yu; Ran Zhao; Runhao Hu; Hui Shen; Jie Cheng; Ge Jiang; Xintong Huang; et al. (Aquaculture International, 2023)

Structural diversity and physicochemical properties of polysaccharides isolated from pumpkin (Cucurbita moschata) by different methods - Xu Jiao; Fei Li; Jing Zhao; Yunlu Wei; Luyao Zhang; Haojie Wang; Wenjun Yu; Quanhong Li (Food Research International, 2023)

Active chitosan/gum Arabic-based emulsion films reinforced with thyme oil encapsulating blood orange anthocyanins: Improving multi-functionality - Runan Zhao; Jin Chen; Songfeng Yu; Ruihao Niu; Zhehao Yang; Han Wang; Huan Cheng; Xingqian Ye; Donghong Liu; Wenjun Wang (Food Hydrocolloids, 2023)

α-D-1,3-glucan from Radix Puerariae thomsonii improves NAFLD by regulating the intestinal flora and metabolites - Qiong Li; Wenjun Liu; Hua Zhang; Chong Chen; Ronghua Liu; Hengwei Hou; Quan Luo; Qinqin Yu; Hui Ouyang; Yulin Feng; Weifeng Zhu (Carbohydrate Polymers, 2023)

Metal mixtures with longitudinal changes in lipid profiles: findings from the manganese-exposed workers healthy cohort - Xiaoting Ge; Guohong Ye; Junxiu He; Yu Bao; Yuan Zheng; Hong Cheng; Xiuming Feng; Wenjun Yang; Fei Wang; Yunfeng Zou; Xiaobo Yang (Environmental Science and Pollution Research, 2022)

Temporal variations, distribution, ecological risks, and sources of antibiotics in the marine ecosystem of Dapeng Cove, Shenzhen, South China - Haochang Su; Wenjun Li; Xiaojuan Hu; Wujie Xu; Yu Xu; Guoliang Wen; Yucheng Cao (Frontiers in Marine Science, 2022)
Introduction Antibiotics are widely used in medical and health services, as well as livestock farming. High concentrations of antibiotics are eventually discarded into rivers due to incomplete metabolism and removal. Bays connect rivers to the sea, and have important ecological functions. Although the occurrence, concentrations, and distribution of antibiotics in bays have been widely studied, the temporal variations in the concentration, contamination indicators and sources of antibiotics, as well as related ecological risk factors, remain unclear. Methods Within this context, we investigate the sources, concentrations, temporal variations, and ecological risks associated with antibiotics in water and sediment samples from Dapeng Cove, Shenzhen, South China, in three rainy seasons. Results Eight and ten different antibiotics were detected in the water and sediment samples, respectively. Of these, the detection rates of erythromycin-H 2 O (ETM) and clarithromycin were highest in both sample types (100%), while trimethoprim (TMP) and ETM were the most abundant antibiotics in the water and sediment samples, respectively. The total concentration (TC) of antibiotics was highest in water and sediment samples from a local domestic sewage site, at 301.96 ng/L and 18.67 ng/g, respectively. Several environmental factors and the concentrations of the predominant antibiotics TMP and ETM were positively correlated. Multiple linear regression analysis revealed TMP and ETM to be the predominant antibiotics influencing the TC of the target antibiotics, with partial regression coefficients of 1.28 and 1.136, respectively ( p < 0.01). Notably, ETM had risk quotients of 0.43–7.91, indicating medium to high risk, while samples from the inner bay and domestic sewage outlet had high ecological risk levels. Redundancy analysis showed that the domestic sewage and inner bay samples were clustered closely but separately from the other samples. Discussion The results of our study indicate that domestic sewage is the dominant source of antibiotics in the bay.

Effect of water temperature on embryonic development of Protunus trituberculatus in an off-season breeding mode - Jie He; Litao Wan; Huaihua Yu; Yingying Peng; Dongxu Zhang; Wenjun Xu (Frontiers in Marine Science, 2022)
Portunus trituberculatus (swimming crab) is an important breeding crab in China. The current breeding mode of swimming crab is still the traditional “spring seedling and winter harvest” breeding mode. In recent years, researchers have begun to explore a new off-season breeding mode through autumn seedling. In this study, the rate of embryonic development, embryo antioxidant ability and hatching rate of swimming crab in different water temperatures in an off-season breeding mode (breeding in early autumn) and digestive enzyme activity of newly hatched larvae were compared. The results showed that the duration of each development stage of swimming crab embryos was gradually reduced with increasing water temperature. The total development time was 9.43 d at 27°C and only 6.88 d at 33°C. These effects were accompanied by an increase in the development rate from 0.11 d -1 to 0.15 d -1 . The total effective accumulated temperature under the 4 temperature conditions was basically maintained at about 150°C·d (147.08 ∼ 153.62°C·d), and there was no significant difference between different groups. The development of embryos at 27°C and 29°C was very synchronous, and no abnormal embryos were observed. Conversely, at 31°C, the later stage of development exhibited asynchrony, and diapause and death were noted in some embryos. At 33°C, more embryos died. The embryo hatching rate was approximately 70% at 27°C and 29°C, and the rate was significantly reduced at 31°C and 33°C. Specifically, the rate was only 13.89% at 33°C. As the water temperature increased, the activities of superoxide dismutase (SOD) and glutathione peroxidase (GSH-PX) as well as the total antioxidant capacity (T-AOC) and malondialdehyde (MDA) levels of embryos increased first and then decreased, reaching the highest value at 31°C. Catalase (CAT) activity exhibited the opposite trend which was the lowest at 29 °C with a value of only 0.17 U/mg prot and the highest at 33°C with a value of up to 0.51 U/mg prot. At temperatures of 27°C, 29°C and 31°C, the differences in various digestive enzymes of newly hatched larvae primarily manifested as the high activities of pepsin (PEP) and α-amylase (AMS) at 31°C, and other differences were not obvious. At 33°C during embryonic development, the activities of various digestive enzymes were relatively low, especially the activities of trypsin (TPS) and cellulase (CL), which were significantly lower than those of the other three temperature groups. Therefore, judging from the antioxidant index of embryos and the digestive enzyme activity of newly hatched larvae, the embryonic development was still good when the water temperature was 31°C, accompanied by water temperatures above 31°C that seriously affected enzyme activity. Overall, a temperature below 31°C represents the appropriate temperature for embryonic development in autumn in swimming crabs.

Association of inflammation and lung function decline caused by personal PM2.5 exposure: a machine learning approach in time-series data - Hao Yu; Tian Xu; Juan Chen; Wenjun Yin; Fang Ye (Environmental Science and Pollution Research, 2022)

A comparative study of the superior longitudinal fasciculus subdivisions between neonates and young adults - Wenjia Liang; Qiaowen Yu; Wenjun Wang; Thijs Dhollander; Emmanuel Suluba; Zhuoran Li; Feifei Xu; Yang Hu; Yuchun Tang; Shuwei Liu (Brain Structure and Function, 2022)
The superior longitudinal fasciculus (SLF) is a complex associative tract comprising three distinct subdivisions in the frontoparietal cortex, each of which has its own anatomical connectivity and functional roles. However, many studies on white matter development, hampered by limitations of data quality and tractography methods, treated the SLF as a single entity. The exact anatomical trajectory and developmental status of each sub-bundle of the human SLF in neonates remain poorly understood. Here, we compared the morphological and microstructural characteristics of each branch of the SLF at two ages using diffusion MRI data from 40 healthy neonates and 40 adults. A multi-shell multi-tissue constrained spherical deconvolution (MSMT-CSD) algorithm was used to ensure the successful separation of the three SLF branches (SLF I, SLF II and SLF III). Then, between-group differences in the diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI) metrics were investigated in all the SLF branches. Meanwhile, Mahalanobis distances based on all the diffusion metrics were computed to quantify the maturation of neonatal SLF branches, considering the adult brain as the reference. The SLF branches, excluding SLF II, had similar fibre morphology and connectivity between the neonatal and adult groups. The Mahalanobis distance values further supported the notion of heterogeneous maturation among SLF branches. The greatest Mahalanobis distance was observed in SLF II, possibly indicating that it was the least mature. Our findings provide a new anatomical basis for the early diagnosis and treatment of diseases caused by abnormal neonatal SLF development.

Comparative Transcriptome and Hormone Analysis of Mature Leaves and New Shoots in Tea Cuttings (Camellia sinensis) among Three Cultivars with Different Rooting Abilities - Kai Fan; Yujie Shi; Danni Luo; Wenjun Qian; Jiazhi Shen; Shibo Ding; Zhaotang Ding; Yu Wang (Journal of Plant Growth Regulation, 2022)

Streptococcus humanilactis sp.nov., isolated from healthy nursing mother's breast milk - Xiaoqing Guo; Fei Han; Lin Cong; Yu Li; Yue Wu; Chen Liu; Jingfang Yang; Risu Na; Wenjun Liu (Archives of Microbiology, 2022)

At what size do anti-injury shelters start to play a positive role in the culture of Portunus trituberculatus? - Jie He; Huaihua Yu; Litao Wan; Dongxu Zhang; Wenjun Xu (Frontiers in Marine Science, 2022)
Based on the existing research, special plastic baskets were used as anti-injury shelters to explore the hidden behavior and molting growth of Portunus trituberculatus (Swimming crab) different initial body weights (Group A: 5.74 ± 0.11 g, Group B: 12.06 ± 0.15 g, Group C: 24.82 ± 0.41 g, Group D: 49.55 ± 1.12 g and Group E: 94.32 ± 1.19 g). The results showed that the shelter occupancy rate (SOR) during the daytime with all different body weights were significantly higher than that at night ( P < 0.05), and the SOR was proportional to the crab’s body weight, among them, SOR in group E was as high as 71.52%. Meanwhile, the territorial consciousness of smaller body weight crabs (Groups A, B and C) was poor, and there was a phenomenon in which multiple individuals occupied the same shelter at the same time, while the individuals with the body weight of approximately 50 g and above (Groups D and E) had strong territorial consciousness, and most of them occupied one shelter alone. In all groups, more individuals chose to molt in the shelter on condition that there existed shelter, and the rate of molting in group B was high up to 81.15% and that in other groups was about 60%. Although the existence of shelter had no significant influence on the molting interphase (MI) of swimming crab in each group, the body weight growth rate (WGR) and carapace width growth rate (WGR C ) after molting were increased by shelter compared with those without shelter. In addition, shelter could improve the survival rate (SR) in each group, and the effect of shelter on individuals with large body weight was relatively more obvious, in which the SR in Group D was significantly improved ( P < 0.05). In general, the shelter can play a positive role in the whole growth of swimming crab. Therefore, it is necessary to set up the shelter in advance before the seedlings are put into production, which is helpful to increase the yield of swimming crab.

Paleo-karst zone and its control on reservoirs in the fourth member of the Sinian Dengying formation in the Moxi area, central Sichuan Basin - Qinyu Xia; Haijun Yan; Wei Xu; Lin Zhang; Qian Li; Wenjun Luo; Hui Deng; Xun Zhu; Xinyu Li; Jichen Yu (Carbonates and Evaporites, 2022)

Biomechanical Analysis of the External Fixation in a Lumbar Fracture Model: A Finite Element Study - Yijia Liao; Yiguo Yan; Yu Kang; Wenjun Wang; Xizheng Song; Wen Peng; Haibin Fu; Huarong Chen; Cheng Wang (Journal of Medical and Biological Engineering, 2022)
Purpose This study aimed to investigate the biomechanical characteristics of the external spinal fixation for treating lumbar fracture through finite element analysis (FEA) and provide a theoretical basis for its further application. Methods Two different models of L3 fracture fixed with the external spinal fixation and the internal fixation system respectively were constructed. The ROM, maximum stresses at L3, and the screws of the two models were measured under load control. Subsequently, the applied torque, the maximum stressed at L3, L1/2, L2/3, L3/4, L4/5 discs and the screws were analyzed under displacement control. Results Under load control, the external fixation model reserved more ROM than the internal fixation model (40.4–48.0% vs 30.5–41.0%). Compared to the internal fixation model, the maximum stresses at L3 and screws in the external fixation model were increased. Under displacement control, the external fixation model required fewer moments (N·mm) than the internal fixation model (flexion: 7500 vs 12,294; extension: 7500 vs 9027). Further, the maximum stresses at L3 and the screws in the external fixation model were greater than those of the internal fixation model, while the maximum stresses at the upper and lower adjacent discs of fixed segments were less than the internal fixation model. Conclusion Compared to the internal fixation system, the external fixation has a better stress distribution with the greater overall mobility. It theoretically reduces the stress concentration of the adjacent discs and the stress shielding of the fractured vertebral body.

Botrytis cinerea BcSSP2 protein is a late infection phase, cytotoxic effector - Wenjun Zhu; Mengxue Yu; Ran Xu; Kai Bi; Shuang Yu; Chao Xiong; Zhiguo Liu; Amir Sharon; Daohong Jiang; Mingde Wu; Qiongnan Gu; Ling Gong; et al. (Environmental Microbiology, 2022)
Summary Botrytis cinerea is a broad‐host‐range necrotrophic phytopathogen responsible for serious diseases in leading crops. To facilitate infection, B . cinerea secretes a large number of effectors that induce plant cell death. In screening secretome data of B . cinerea during infection stage, we identified a phytotoxic protein (BcSSP2) that can also induce immune resistance in plants. BcSSP2 is a small, cysteine‐rich protein without any known domains. Transient expression of BcSSP2 in leaves caused chlorosis that intensifies with time and eventually leads to death. Point mutations in eight of 10 cysteine residues abolished phytotoxicity, but residual toxic activity remained after heating treatment, suggesting contribution of unknown epitopes to protein phytotoxicity. The expression of bcssp2 was low during the first 36 h after inoculation and increased sharply upon transition to late infection stage. Deletion of bcssp2 did not cause statistically significant changes in lesions size on bean and tobacco leaves. Further analyses indicated that the phytotoxicity of BcSSP2 is negatively regulated by the receptor‐like kinases BAK1 and SOBIR1. Collectively, our findings show that BcSSP2 is an effector protein that toxifies the host cells, but is also recognized by the plant immune system.

Comparing the Muscle Nutritional Quality of Eight Common Wild-Caught Economic Shrimp Species from the East China Sea - Litao Wan; Yingying Peng; Huaihua Yu; Wenjun Xu; Jie He (Journal of Aquatic Food Product Technology, 2022)

Important role of the ENSO combination mode in the maintenance of the anomalous anticyclone over the western North Pacific in boreal summer - Wenjun Zhang; Zuoli Yu; Feng Jiang; Xin Geng; Renhe Zhang (Science China Earth Sciences, 2022)

Arsenic trioxide increases apoptosis of SK-N-BE (2) cells partially by inducing GPX4-mediated ferroptosis - Chuchu Feng; Yu Wu; Yantao Chen; Xilin Xiong; Peng Li; Xiaomin Peng; Chunmou Li; Wenjun Weng; Yafeng Zhu; Dunhua Zhou; Yang Li (Molecular Biology Reports, 2022)

Optimize the irrigation and fertilizer schedules by combining DSSAT and genetic algorithm - Yu Bai; Wenjun Yue; Chunmei Ding (Environmental Science and Pollution Research, 2022)

Microcredit programs may increase risk to pastoralist livelihoods in Inner Mongolia - Yu Lu; Lynn Huntsinger; WenJun Li (Ambio, 2022)

Association between ozone exposure and prevalence of mumps: a time-series study in a Megacity of Southwest China - Wenjun Xie; Han Zhao; Chang Shu; Bin Wang; Wen Zeng; Yu Zhan (Environmental Science and Pollution Research, 2021)

Association of systemic inflammation indices with visual field loss progression in patients with primary angle-closure glaucoma: potential biomarkers for 3P medical approaches - Shengjie Li; Yichao Qiu; Jian Yu; Mingxi Shao; Yingzhu Li; Wenjun Cao; Xinghuai Sun (EPMA Journal, 2021)

Aquiflexum lacus sp. nov., isolated from a lake sediment sample - Jianrong Huang; Mingxian Han; Baozhu Fang; Jian Yang; Haiyi Xiao; Xiying Zhang; Jibin Han; Dongmei Yu; Hongchen Jiang; Wenjun Li (Archives of Microbiology, 2021)

Molecular Evolution and Local Root Heterogeneous Expression of the Chenopodium quinoa ARF Genes Provide Insights into the Adaptive Domestication of Crops in Complex Environments - Wenjun Sun; Haomiao Yu; Zhaotang Ma; Yuan Yuan; Sijiao Wang; Jun Yan; Xinran Xu; Hui Chen (Journal of Molecular Evolution, 2021)

Reservoir protection and well completion technology for multi-branch horizontal wells in coalbed methane - Xiaofeng Ran; Bo Zhang; Wei Wei; Haifa Yu; Wenjun Liang; Kai Wei (Arabian Journal of Geosciences, 2021)

Mortality burden caused by diurnal temperature range: a nationwide time-series study in 364 Chinese locations - Min Cai; Jianxiong Hu; Chunliang Zhou; Zhulin Hou; Yanjun Xu; Maigeng Zhou; Yize Xiao; Biao Huang; Xiaojun Xu; Lifeng Lin; Tao Liu; Jianpeng Xiao; et al. (Stochastic Environmental Research and Risk Assessment, 2021)

EEG-Based Anxious States Classification Using Affective BCI-Based Closed Neurofeedback System - Chao Chen; Xuecong Yu; Abdelkader Nasreddine Belkacem; Lin Lu; Penghai Li; Zufeng Zhang; Xiaotian Wang; Wenjun Tan; Qiang Gao; Duk Shin; Changming Wang; Sha Sha; et al. (Journal of Medical and Biological Engineering, 2021)

Aging exacerbates impairments of cerebral blood flow autoregulation and cognition in diabetic rats - Shaoxun Wang; Wenshan Lv; Huawei Zhang; Yedan Liu; Longyang Li; Joshua R. Jefferson; Ya Guo; Man Li; Wenjun Gao; Xing Fang; Ian A. Paul; Grazyna Rajkowska; et al. (GeroScience, 2020)

Safe utilization and zoning on natural selenium-rich land resources: a case study of the typical area in Enshi County, China - Tao Yu; Wanling Hou; Qingye Hou; Wenjun Ma; Xueqi Xia; Yutong Li; Beizhan Yan; Zhongfang Yang (Environmental Geochemistry and Health, 2020)

Erosion-deposition patterns and depo-center movements in branching channels at the near-estuary reach of the Yangtze River - Boyuan Zhu; Jinyun Deng; Jinwu Tang; Wenjun Yu; Alistair G. L. Borthwick; Yuanfang Chai; Zhaohua Sun; Yitian Li (Frontiers of Earth Science, 2020)

Comparison of the aridity index and its drivers in eight climatic regions in China in recent years and in future projections - Yanzhong Li; Wenjun Yu; Kaiwen Wang; Xieyao Ma (International Journal of Climatology, 2019)
Intense anthropogenic climate changes are expected to increase atmospheric aridity in the 21st century. The aridity index (AI), defined as the ratio of annual precipitation ( P re ) to atmospheric evaporation (potential evapotranspiration [PET]), represents an efficient indicator of climatic changes. However, the variations and underlying drivers of AI values have not been comprehensively compared in different climatic regions. Using the AI calculated on the basis of bias‐corrected precipitation and optimized PET over the period of 1999–2017 and two climate model projections for the coming century, we investigated the response of the AI to climate change and quantified the contributions of climatic factors to AI variations in eight climatic regions in China, that is, the northwest (NW), north‐centre (NC), northeast (NE), North China Plain (NCP), east (E), southeast (SE), southwest (SW) and Tibet Plateau (TP). The results indicated that the AI values in seven of the eight climate regions exhibited negative trends from 1999 to 2017, with mean values ranging from −0.0008 in SW to −0.0414 in NC, while the AI values in the TP region showed a significant positive trend, with a value of 0.0124. P re was the dominant factor for the variations in AI values in all climate regions, with contribution rates from 65 to 308%, followed by decreasing solar radiation in the NW, NC, E, SE and SW regions; deceasing wind speed in NE and NCP; and deceasing actual vapour pressure in the TP. The effect of increasing temperature on the AI trend was offset by other climate factors. By the end of the 21st century, under the Representative Concentration Pathway 8.5 emission scenario, the AI will significantly increase in five of the eight regions to values approximately 16.5% higher than those during 1999–2017, and this increase in the AI will be dominated by increasing PET. Overall, the shift in the dominant AI factor from P re in recent years to PET in the future indicates that more attention should be given to the response of the AI to global warming. Furthermore, regional differences in climate change and AI values during 2018–2,100 will inevitably influence water availability and urgently require the development of adaptation strategies for different climatic regions.

Laboratory investigation into the oil diffusion from submarine pipeline under water flow - Meirong Jiang; Jianxing Yu; Zhigang Li; Wenjun Zhong; Zhaohui Wu; Yang Yu (Acta Oceanologica Sinica, 2018)

Effects of Litter Inputs on N2O Emissions from a Tropical Rainforest in Southwest China - Jinbo Gao; Wenjun Zhou; Yuntong Liu; Jing Zhu; Liqing Sha; Qinhai Song; Hongli Ji; Youxing Lin; Xuehai Fei; Xiaolong Bai; Xiang Zhang; Yun Deng; et al. (Ecosystems, 2018)

Synaptobrevin-2 facilitates the trafficking and function of atrial SK2 channel - Tao Li; Xuehui Fan; Yiyan Yu; Linlin Chen; Wenjun Huang; Yan Yang; Jimin Cao; Xiaorong Zeng; Xiaoqiu Tan (Science China Life Sciences, 2018)

Geological effects influence population genetic connectivity more than Pleistocene glaciations in the water strider Metrocoris sichuanensis (Insecta: Hemiptera: Gerridae) - Zhen Ye; Juanjuan Yuan; Min Li; Jakob Damgaard; Pingping Chen; Chenguang Zheng; Haibin Yu; Siying Fu; Wenjun Bu (Journal of Biogeography, 2018)
Aim Palaeoclimatic and palaeogeological events have been identified as two main factors that influence the genetic structuring of extant organisms. We studied a montane stream‐dwelling insect, Metrocoris sichuanensis , to explore the relative roles played by these two factors in population genetic connectivity. Location Sichuan Basin, China. Methods Mitochondrial ( COI , COII , Cytb, 16S) and nuclear ( EF ‐1α, ITS 1) markers were sequenced from 208 individuals. Suitable habitat shifts from the Last Glacial Maximum ( LGM ) to the present were predicted through fine‐tuned ecological niche modelling ( ENM ). Phylogenetic and phylogeographical analyses were conducted to reveal the population genetic structure. Intraspecific divergence and expansion times were estimated using beast . Finally, the least cost path ( LCP ) method coupled with migrate analysis was used to identify possible dispersal corridors and estimate the asymmetric gene flow. Results Our ENM results suggested that population habitat connectivity did not change both in the LGM and current conditions. Whole haplotypes were separated into four highly supported clades/haplogroups that exhibited strong geographical structure. The splitting events between the four lineages likely date back to the Early Pleistocene. Bayesian skyline plot ( BSP ) indicated a moderate demographic growth from the LGM to the present. A putative dispersal corridor was detected along the Longmen Mountains thrust belt, with unidirectional gene flow from north to south. Main conclusion Our findings support the geographical isolation of the genetic lineages and a deep early Pleistocene split in M. sichuanensis . Landscape connectivity analysis incorporating the genetic data and the ENM prediction revealed that population genetic connectivity was strongly associated with stable climatic habitats shaped by complex topography. The drainage system might have assisted the rapid movement of populations along the Longmen Mountains thrust belt. A strategy for researching the population genetic connectivity of narrow endemics, such as M. sichuanensis , in global biodiversity hotspots is proposed and discussed in this paper.

Vitamin K2 inhibits rat vascular smooth muscle cell calcification by restoring the Gas6/Axl/Akt anti-apoptotic pathway - Cuiting Qiu; Haijun Zheng; Huiren Tao; Wenjun Yu; Xiaoyu Jiang; Aiqin Li; Hui Jin; Anlin Lv; Huan Li (Molecular and Cellular Biochemistry, 2017)

Using an unmanned aerial vehicle for topography mapping of the fault zone based on structure from motion photogrammetry - Haiyun Bi; Wenjun Zheng; Zhikun Ren; Jiangyuan Zeng; Jingxing Yu (International Journal of Remote Sensing, 2017)

Population genetics and ecological niche modeling shed light on conservation of the island endemic damselfly Pseudolestes mirabilis (Odonata, Pseudolestidae) - Junli Xue; Xin Yu; Haiguang Zhang; Xin Chen; Wenjun Bu (Hydrobiologia, 2017)

Cardiac-Specific Knockout of ETA Receptor Mitigates Paraquat-Induced Cardiac Contractile Dysfunction - Jiaxing Wang; Songhe Lu; Qijun Zheng; Nan Hu; Wenjun Yu; Na Li; Min Liu; Beilei Gao; Guoyong Zhang; Yingmei Zhang; Haichang Wang (Cardiovascular Toxicology, 2016)

Dextral strike-slip of Sanguankou-Niushoushan fault zone and extension of arc tectonic belt in the northeastern margin of the Tibet Plateau - QiYun Lei; PeiZhen Zhang; WenJun Zheng; ChiZhang Chai; WeiTao Wang; Peng Du; JingXing Yu (Science China Earth Sciences, 2016)

Hydrological Responses to Land-Use Change Scenarios under Constant and Changed Climatic Conditions - Ling Zhang; Zhuotong Nan; Wenjun Yu; Yingchun Ge (Environmental Management, 2016)

Modeling Land-Use and Land-Cover Change and Hydrological Responses under Consistent Climate Change Scenarios in the Heihe River Basin, China - Ling Zhang; Zhuotong Nan; Wenjun Yu; Yingchun Ge (Water Resources Management, 2015)

Protective effect of berberine against myocardial ischemia reperfusion injury: role of Notch1/Hes1-PTEN/Akt signaling - Liming Yu; Feijiang Li; Guolong Zhao; Yang Yang; Zhenxiao Jin; Mengen Zhai; Wenjun Yu; Lin Zhao; Wensheng Chen; Weixun Duan; Shiqiang Yu (Apoptosis, 2015)

A biophysically based and objective satellite seasonality observation method for applications over the Arctic - Wenjun Chen; Norah Foy; Ian Olthof; Yu Zhang; Robert Fraser; Rasim Latifovic; Jean Poitevin; Paul Zorn; Donald McLennan (International Journal of Remote Sensing, 2014)

Effects of urbanization on daily temperature extremes in North China - Peng Si; Zuofang Zheng; Yu Ren; Dongpo Liang; Mingcai Li; Wenjun Shu (Journal of Geographical Sciences, 2014)

Distribution of phthalate esters in topsoil: a case study in the Yellow River Delta, China - Yang Hongjun; Xie Wenjun; Liu Qing; Liu Jingtao; Yu Hongwen; Lu Zhaohua (Environmental Monitoring and Assessment, 2013)

Opposing functions of PLAG1 in pleomorphic adenoma: a microarray analysis of PLAG1 transgenic mice - Yang Wang; Wenjun Shang; Xia Lei; Shukun Shen; Hongxin Zhang; Zhugang Wang; Lei Huang; Zhiwei Yu; Huishan Ong; Xuelai Yin; Wenjun Yang; Chenping Zhang (Biotechnology Letters, 2013)

The biochemical and immunological characterization of two serpins from Clonorchis sinensis - Huali Lei; Yanli Tian; Wenjun Chen; Xiaoyun Wang; Xuerong Li; Qiang Mao; Jiufeng Sun; Ran Li; Yanquan Xu; Chi Liang; Yan Huang; Xinbing Yu (Molecular Biology Reports, 2013)

Lentivirus-mediated gene silencing of KLF8 reduced the proliferation and invasion of gastric cancer cells - Gang Chen; Wenjun Yang; Weidong Jin; Yi Wang; Chonglin Tao; Zhengping Yu (Molecular Biology Reports, 2012)

Molecular identification and characterization of leucine aminopeptidase 2, an excretory-secretory product of Clonorchis sinensis - Chuanhuan Deng; Jiufeng Sun; Xuerong Li; Lexun Wang; Xuchu Hu; Xiaoyun Wang; Wenjun Chen; Xiaoli Lv; Chi Liang; Wenfang Li; Yan Huang; Ran Li; et al. (Molecular Biology Reports, 2012)

IL6 gene polymorphisms and susceptibility to colorectal cancer: a meta-analysis and review - Yong Yu; Wenjun Wang; Song Zhai; Shuangsuo Dang; Mingzhu Sun (Molecular Biology Reports, 2012)

Dual effects of sodium butyrate on hepatocellular carcinoma cells - Wenjun Jiang; Qiya Guo; Jun Wu; Bin Guo; Yingming Wang; Shenan Zhao; Huiling Lou; Xin Yu; Xinyu Mei; Chaoqun Wu; Shouyi Qiao; Yanhua Wu (Molecular Biology Reports, 2012)

Influence of Novel Nano-Mesoporous Bioactive Glass on the Regulation of IGF-II Gene Expression in Osteoblasts - Zhang Quan; Xie Han; Zhang Ye; Yu Chenzhong; Chen Wenjun (Cell Biochemistry and Biophysics, 2012)

A preliminary phylogenetic study of Megapodagrionidae with focus on the Chinese genera Sinocnemis Wilson & Zhou and Priscagrion Zhou & Wilson (Odonata: Zygptera) - Xin Yu; Wenjun Bu (Hydrobiologia, 2011)

Biomass measurements and relationships with Landsat‐7/ETM+ and JERS‐1/SAR data over Canada's western sub‐arctic and low arctic - Wenjun Chen; D. Blain; Junhua Li; K. Keohler; R. Fraser; Yu Zhang; S. Leblanc; I. Olthof; Jixin Wang; M. McGovern (International Journal of Remote Sensing, 2009)